Method for manufacturing raw material roll of circular polarizing plate, and raw material roll of circular polarizing plate
By controlling the shear stress of the active energy ray curing adhesive and the rigidity of the protective film during the manufacturing process of the circular polarization plate, the problem of low yield of circular polarization plates in the prior art is solved, and a higher yield and stability are achieved.
Patent Information
- Application Number
- CN202411400546.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-12
- Filing Date
- 2024-10-09
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, there is room for improvement in the yield of the circular polarizing plate as a monolithic body.
A method for manufacturing a raw material roll of a circular polarization plate is adopted, including preparing an optical laminate, irradiating an active energy ray to cure the adhesive layer, and making the optical laminate with the surface of the transport roller during the transport process. This method controls the shear stress of the active energy ray curing adhesive and the rigidity of the protective film to improve the yield.
Through this method, the yield of the monolithic circular polarizing plate is significantly improved, and the stability and bonding strength of the optical laminate are ensured.
Smart Images

Figure CN119823659A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a raw material roll of a circular polarizing plate and a raw material roll of a circular polarizing plate. Background Art
[0002] Conventionally, there is known a circularly polarizing plate in which a polarizing laminate including a linear polarizing plate and a phase element including a liquid crystal phase difference layer are bonded together via a cured layer of an active energy ray-curable adhesive.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2014-28976 Summary of the invention
[0006] Problems to be solved by the invention
[0007] However, in the prior art, the yield of circularly polarizing plates as a single piece has room for improvement.
[0008] The present invention has been made in view of the above problems, and an object of the present invention is to provide a method for manufacturing a circular polarizing plate stock roll and a circular polarizing plate stock roll capable of improving the yield of a circular polarizing plate as a single body.
[0009] Means for solving problems
[0010] [1] A method for manufacturing a circular polarizing plate raw material roll, comprising:
[0011] A step of preparing an optical laminate, the optical laminate comprising, in order, a polarizing laminate, a layer of an active energy ray-curable adhesive, a phase element comprising one or more liquid crystal phase difference layers, and a substrate layer, the polarizing laminate comprising a linear polarizer and one or more protective films;
[0012] a step of irradiating the optical layered body with active energy rays to cure the layer of the active energy ray-curable adhesive; and
[0013] a step of conveying the optical layered body while bringing the optical layered body into contact with the surface of at least one conveying roller after the irradiation;
[0014] The cured product of the active energy ray-curable adhesive has a shear stress α of 100 Pa or less at 25° C.,
[0015] The shear stress α is the maximum stress when a cured product of the active energy ray-curable adhesive having a circular plate shape of 8 mm in diameter and 5 μm in thickness is clamped by a pair of parallel plates and vibrated about the central axis of the circular plate at a rotation angle of 1 mrad and a frequency of 1 Hz to impart a torsional moment.
[0016] The total rigidity value of each of the protective films in the polarizing laminate is 250000 N / m or less.
[0017] In the above-mentioned conveying step, at least one conveying roller is in contact with the above-mentioned polarizing laminate of the above-mentioned optical laminate, and the wrap angle (Japanese: wrap angle) of the conveying roller in contact with the above-mentioned polarizing laminate of the above-mentioned optical laminate is 150 degrees or less,
[0018] In the above-mentioned conveying process, when at least one conveying roller is in contact with the above-mentioned substrate layer of the above-mentioned optical layered body and the rigidity value of the above-mentioned substrate layer is less than 250000 N / m, further in the above-mentioned conveying process, the wrap angle of the conveying roller in contact with the above-mentioned substrate layer of the above-mentioned optical layered body is less than 150°.
[0019] [2] The method according to [1], wherein in the irradiation step, the optical layered body is irradiated with the active energy ray from the substrate layer side.
[0020] [3] A circular polarizing plate raw material roll, which comprises, in order, a polarizing laminate, a layer of a cured product of an active energy ray-curable adhesive, and a phase element comprising one or more liquid crystal phase difference layers, wherein the polarizing laminate has a linear polarizer and one or more protective films,
[0021] The total rigidity value of each of the protective films in the polarizing laminate is 250000 N / m or less.
[0022] The cured product of the active energy ray-curable adhesive has a shear stress α of 100 Pa or less at 25° C.,
[0023] The shear stress α is the maximum stress when a cured product of the active energy ray-curable adhesive having a circular plate shape of 8 mm in diameter and 5 μm in thickness is clamped by a pair of parallel plates and vibrated about the central axis of the circular plate at a rotation angle of 1 mrad and a frequency of 1 Hz to impart a torsional moment.
[0024] The surface of the layer of the cured product of the active energy ray-curable adhesive on the side facing the polarizing laminate does not have recessed portions having a maximum depth exceeding 500 nm periodically formed along the longitudinal direction of the circularly polarizing plate.
[0025] [4] A raw material roll of a circular polarizing plate according to [3], wherein the surface of the layer of the cured product of the active energy ray-curable adhesive on the side opposite to the phase element does not have recesses with a maximum depth exceeding 500 nm periodically formed along the length direction of the circular polarizing plate.
[0026] Effects of the Invention
[0027] According to the present invention, there are provided a method for manufacturing a circularly polarizing plate raw material roll and a circularly polarizing plate raw material roll capable of improving the yield of a single sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic cross-sectional view of a laminate in one embodiment of the production method.
[0029] Figure 2 (a) to (d) represent Figure 1 Schematic cross-sectional view of an example of a polarizing stack 30 .
[0030] Figure 3 (a) to (d) represent Figure 1 Schematic cross-sectional view of another example of the polarizing stack 30 .
[0031] Figure 4 (a) and (b) represent Figure 1 FIG. 1 is a schematic cross-sectional view of an example of a stacked structure of a phase element 50 and a base layer 80 .
[0032] Figure 5 It is a schematic diagram showing a conveying system in the manufacturing method.
[0033] Figure 6 It is a schematic cross-sectional view of one embodiment of the circular polarizing plate 100 ′.
[0034] Figure 7 This is an example of a cross-sectional curve of the surface of the layer 40 ′ of the cured product of the active energy ray-curable adhesive of the circularly polarizing plate 100 ′ obtained by the optical interference method. DETAILED DESCRIPTION
[0035] The method for producing a circularly polarizing plate raw material roll according to the embodiment of the present invention includes the following steps.
[0036] (1) a step of preparing an optical laminate, wherein the optical laminate comprises, in order, a polarizing laminate, a layer of an active energy ray-curable adhesive, a phase element comprising one or more liquid crystal phase difference layers, and a substrate layer, wherein the polarizing laminate comprises a linear polarizer and one or more protective films
[0037] (2) a step of irradiating the optical layered body with active energy rays to cure the layer of the active energy ray-curable adhesive.
[0038] (3) After the irradiation, the optical layered body is transported while being brought into contact with the surface of at least one transport roller.
[0039] Step (1) Preparation of optical laminate
[0040] like Figure 1 As shown, the optical laminate 100 includes a polarizing laminate 30 , an active energy ray-curable adhesive layer 40 , a phase element 50 , and a base layer 80 in this order.
[0041] (Polarizing laminate 30)
[0042] The polarizing laminate 30 includes a linear polarizer and one or more protective films.
[0043] (Linear polarizer)
[0044] Examples of the linear polarizing plate are a PVA-based linear polarizing plate and a liquid crystal coating type linear polarizing plate.
[0045] (PVA linear polarizer)
[0046] PVA-based linear polarizers are usually manufactured through the following steps: a step of uniaxially stretching a polyvinyl alcohol-based resin film (hereinafter, also referred to as a PVA-based film); a step of dyeing the PVA-based film with a dichroic dye to adsorb the dichroic dye; a step of treating the PVA-based film adsorbed with the dichroic dye with an aqueous boric acid solution to cross-link it; and a step of washing with water after the cross-linking treatment with an aqueous boric acid solution (hereinafter, also referred to as a boric acid treatment).
[0047] The polyvinyl alcohol resin (hereinafter also referred to as "PVA resin") constituting the PVA film can be produced by saponifying a polyvinyl acetate resin. In addition to polyvinyl acetate which is a homopolymer of vinyl acetate, the polyvinyl acetate resin may also be a copolymer of vinyl acetate and other monomers copolymerizable with vinyl acetate. Other monomers copolymerizable with vinyl acetate include, for example, unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, (meth)acrylamides having an ammonium group, and the like. It should be noted that, in the present specification, "(meth)acrylic acid" refers to any of acrylic acid and methacrylic acid. The "(meth)" of (meth)acrylates, etc., also has the same meaning.
[0048] The saponification degree of PVA resin is usually about 85 to 100 mol%, preferably 98 mol% or more. PVA resin can be modified, for example, polyvinyl formal, polyvinyl acetal, etc. modified by aldehydes can also be used. The average polymerization degree of PVA resin is usually about 1000 to 10000, preferably about 1500 to 5000. The average polymerization degree of PVA resin can be calculated according to JIS K 6726 (1994). If the average polymerization degree is less than 1000, it is difficult to obtain the preferred polarization performance. If it exceeds 10000, the film processability is sometimes poor.
[0049] The uniaxial stretching of the PVA film can be performed before, at the same time as, or after dyeing with a dichroic dye. In the case of uniaxial stretching after dyeing, the uniaxial stretching can be performed before or during the boric acid treatment. Of course, uniaxial stretching can also be performed in the multiple stages shown here. The uniaxial stretching can be performed by a method of uniaxial stretching along the film conveying direction between rollers with different peripheral speeds, a method of uniaxial stretching along the film conveying direction using a hot roller, a method of stretching along the width direction using a tenter, etc. In addition, the uniaxial stretching can be performed by dry stretching in the atmosphere, or by wet stretching in a state where the PVA film is swollen using a solvent such as water. The stretching ratio is usually about 3 to 8 times.
[0050] The dyeing utilizing the dichroic pigment of the PVA system film can be carried out by, for example, dipping the PVA system film in an aqueous solution containing the dichroic pigment. As the dichroic pigment, specifically, iodine or dichroic organic dyes can be used. It should be noted that the PVA system film is preferably immersed in water in advance before the dyeing process to make it swell.
[0051] When iodine is used as a dichroic pigment, a method of dyeing the PVA film by immersing it in an aqueous solution containing iodine and potassium iodide is generally adopted. The content of iodine in the aqueous solution is generally about 0.01 to 1 mass part relative to 100 mass parts of water, and the content of potassium iodide is generally about 0.5 to 20 mass parts relative to 100 mass parts of water. The temperature of the aqueous solution used in dyeing is generally about 20 to 40° C. In addition, the immersion time (dyeing time) in the aqueous solution is generally about 20 to 1,800 seconds.
[0052] On the other hand, when using a dichroic organic dye as a dichroic pigment, a method of dyeing by immersing the PVA film in an aqueous solution containing a water-soluble dichroic organic dye is generally adopted. The content of the dichroic organic dye in the aqueous solution is generally about 0.0001 to 10 parts by mass relative to 100 parts by mass of water, preferably 0.001 to 1 part by mass. The dye aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing auxiliary. The temperature of the dichroic organic dye aqueous solution used in dyeing is generally about 20 to 80° C. In addition, the immersion time (dyeing time) in the aqueous solution is generally about 10 to 1,800 seconds.
[0053] Boric acid treatment after dyeing with a dichroic pigment can be carried out by immersing the dyed PVA film in an aqueous solution containing boric acid. The content of boric acid in the aqueous solution containing boric acid is generally about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. In the case of using iodine as a dichroic pigment, the aqueous solution containing boric acid preferably contains potassium iodide. The content of potassium iodide in the aqueous solution containing boric acid is generally about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. The immersion time in the aqueous solution containing boric acid is generally about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the aqueous solution containing boric acid is generally above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0054] The PVA film after the boric acid treatment is usually subjected to a water washing treatment. The water washing treatment can be performed, for example, by immersing the PVA film treated with boric acid in water. The temperature of the water in the water washing treatment is usually about 5 to 40° C. In addition, the immersion time is usually about 1 to 120 seconds.
[0055] After washing, drying treatment is implemented to obtain a polarizer. Drying treatment can be carried out using a hot air dryer or a far infrared heater. The temperature of the drying treatment is usually about 30 to 100° C., preferably 50 to 80° C. The time of the drying treatment is usually about 60 to 600 seconds, preferably 120 to 600 seconds. By drying treatment, the moisture content in the polarizer is reduced to a practical level. Its moisture content is usually about 5 to 20% by mass relative to the total mass of the polarizer, preferably 8 to 15% by mass. If the moisture content is 5% by mass or more, the polarizer has sufficient flexibility, so it can suppress damage or breakage after drying. In addition, if the moisture content is less than 20% by mass, the polarizer has sufficient thermal stability.
[0056] (PVA-based linear polarizing plate)
[0057] An example of a polarizing laminate (linear polarizing plate) 30 in which the linear polarizer is a stretched polyvinyl alcohol-based resin containing a dichroic dye is as follows: Figure 2 As shown in (a), a first polarizing plate protective film (protective film) 34, a linear polarizing plate 32 and a second polarizing plate protective film (protective film) 36 are provided in this order. Figure 2 In the whole, the lower side of the polarization stack 30 is Figure 1 The second polarizer protective film 36 is in contact with the layer 40 of the active energy ray-curable adhesive. In the present embodiment, the second polarizer protective film 36 is in contact with the layer 40 of the active energy ray-curable adhesive.
[0058] Another example of the polarizing laminate (linear polarizing plate) 30 in which the linear polarizer is a stretched polyvinyl alcohol-based resin containing a dichroic dye is as follows Figure 2 As shown in (b), a first polarizer protective film (protective film) 34 and a linear polarizer 32 are provided. In the present embodiment, the linear polarizer 32 is in contact with a layer 40 of an active energy ray-curable adhesive.
[0059] The thickness of the linear polarizing plate 32 in the case of stretched PVA is usually 5 to 80 μm.
[0060] exist Figure 2 In (a) and (b), there may be a first polarizer adhesive layer 38 and a second polarizer adhesive layer 39 between the linear polarizer 32 and the first polarizer protective film 34, and between the linear polarizer 32 and the second polarizer protective film 36, respectively.
[0061] (Polarizing Plate Adhesive Layer)
[0062] The first polarizer adhesive layer 38 and the second polarizer adhesive layer 39 can have a function of bonding the linear polarizer 32 to the polarizer protective films 34 and 36. The adhesive layer can be formed of an adhesive composition.
[0063] Examples of adhesive compositions include water-based adhesive compositions, curable adhesive compositions that cure by heating or irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays, etc. Examples of water-based adhesive compositions include compositions obtained by dissolving a polyvinyl alcohol-based resin or a urethane resin as a main component in water, and compositions obtained by dispersing a polyvinyl alcohol-based resin or a urethane resin as a main component in water. The water-based adhesive composition may further contain curable components such as polyaldehydes, melamine-based compounds, zirconium oxide compounds, zinc compounds, glyoxal compounds, and water-soluble epoxy resins, and crosslinking agents. Examples of the water-based adhesive composition include the adhesive composition described in JP-A-2010-191389, the adhesive composition described in JP-A-2011-107686, the composition described in JP-A-2020-172088, and the composition described in JP-A-2005-208456.
[0064] The curable adhesive composition is preferably an active energy ray-curable adhesive composition that contains a curable (polymerizable) compound as a main component and is cured by irradiation with active energy rays. Examples of the active energy ray-curable adhesive composition include a cationic polymerizable adhesive composition containing a cationic polymerizable compound as a curable compound, a free radical polymerizable adhesive composition containing a free radical polymerizable compound as a curable compound, and a mixed adhesive composition containing both a cationic polymerizable compound and a free radical polymerizable compound as curable compounds.
[0065] The cationically polymerizable compound is a compound or oligomer that is cured by cation polymerization reaction when irradiated with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays or heated, and specific examples thereof include epoxy compounds, oxetane compounds, and vinyl compounds.
[0066] Examples of epoxy compounds include: alicyclic epoxy compounds (compounds having one or more epoxy groups bonded to an alicyclic ring in the molecule) such as 3,4-epoxycyclohexanecarboxylic acid 3',4'-epoxycyclohexylmethyl ester; aromatic epoxy compounds (compounds having an aromatic ring and an epoxy group in the molecule) such as diglycidyl ether of bisphenol A; aliphatic epoxy compounds (compounds having at least one oxirane ring bonded to an aliphatic carbon atom in the molecule) such as 2-ethylhexyl glycidyl ether and 1,4-butanediol diglycidyl ether, etc.
[0067] Examples of the oxetane compound include compounds having one or more oxetane rings in the molecule, such as 3-ethyl-3-{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane.
[0068] The cationic polymerization adhesive composition preferably contains a cationic polymerization initiator. The cationic polymerization initiator may be a thermal cationic polymerization initiator or a photocationic polymerization initiator. Examples of cationic polymerization initiators include aromatic diazonium salts such as benzene diazonium hexafluoroantimonate; aromatic iodonium salts such as diphenyl iodonium tetrakis (pentafluorophenyl) borate; aromatic sulfonium salts such as triphenyl sulfonium hexafluorophosphate; iron-aromatic complexes such as ditoluene-cyclopentadienyl iron (II) hexafluoroantimonate, etc. The content of the cationic polymerization initiator is generally 0.1 to 10 parts by mass relative to 100 parts by mass of the cationic polymerization compound. Two or more cationic polymerization initiators may be included.
[0069] Examples of the cationically polymerizable adhesive composition include cationically polymerizable compositions described in JP-A-2016-126345, WO-2019 / 10315, and JP-A-2021-113969.
[0070] The free radical polymerizable compound is a compound or oligomer that is cured by free radical polymerization reaction by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays, or heating, and specifically, a compound having an ethylenically unsaturated bond can be cited. As the compound having an ethylenically unsaturated bond, a (meth)acrylic compound having one or more (meth)acryloyl groups in the molecule, a vinyl compound having one or more vinyl groups in the molecule, etc. can be cited.
[0071] Examples of the (meth)acrylic compound include (meth)acrylic oligomers having at least two (meth)acrylic groups in a molecule obtained by reacting two or more (meth)acrylic acid ester monomers, (meth)acrylamide monomers, and functional group-containing compounds. In the present specification, the (meth)acrylic group may be either an acryloyl group or a methacryloyl group.
[0072] The radical polymerization adhesive composition preferably contains a radical polymerization initiator. The radical polymerization initiator may be a thermal radical polymerization initiator or a photoradical polymerization initiator. Examples of the radical polymerization initiator include: acetophenone-based initiators such as acetophenone and 3-methylacetophenone; benzophenone-based initiators such as benzophenone, 4-chlorobenzophenone, and 4,4'-diaminobenzophenone; benzoin ether-based initiators such as benzoin propyl ether and benzoin ethyl ether; thioxanthone-based initiators such as 4-isopropylthioxanthone; xanthones, fluorenones, etc. The content of the radical polymerization initiator is generally 0.1 to 10 parts by mass relative to 100 parts by mass of the radical polymerizable compound. Two or more radical polymerization initiators may be included.
[0073] Examples of the radical polymerizable adhesive composition include radical polymerizable compositions described in JP-A-2016-126345, JP-A-2016-153474, and International Publication No. 2017 / 183335.
[0074] The active energy ray-curable adhesive composition may contain additives such as ion trapping agents, antioxidants, chain transfer agents, tackifiers, thermoplastic resins, fillers, flow regulators, plasticizers, defoamers, antistatic agents, leveling agents, and solvents as necessary.
[0075] The bonding of the linear polarizer 32 to the first polarizer protective film 34 and the second polarizer protective film 36 using an adhesive layer can be carried out as follows: an adhesive composition is applied to at least one bonding surface selected from the bonding surface of the linear polarizer and the bonding surface of each polarizer protective film, the two are overlapped with the aid of the coating layer of the adhesive composition, and after bonding them from top and bottom using a bonding roller, the adhesive layer is dried, irradiated with active energy rays to cure it, or heated to cure it.
[0076] Before forming the adhesive layer coating, at least one of the bonding surfaces of the linear polarizer and the polarizer protective film may be subjected to an adhesion-facilitating treatment such as saponification treatment, corona treatment, plasma treatment, primer treatment, anchor coating treatment, etc.
[0077] The coating layer of the adhesive composition can be formed by various coating methods such as a die coater, a comma coater, a gravure coater, a wire bar coater, and a knife coater.
[0078] The light irradiation intensity during irradiation with active energy rays is determined according to the composition of the active energy ray-curable adhesive composition and is not particularly limited, but is preferably 10 mW / cm 2 Above 1,000mW / cm 2 It should be noted that the irradiation intensity is preferably an intensity in the wavelength region effective for the activation of the photocationic polymerization initiator or the photoradical polymerization initiator. The irradiation is performed once or multiple times with such a light irradiation intensity, and the accumulated light amount is preferably set to 10 mJ / cm 2 More preferably, 100 mJ / cm 2 Above and 1,000mJ / cm 2 the following.
[0079] The light source used for polymerizing and curing the active energy ray-curable adhesive composition is not particularly limited, and examples thereof include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.
[0080] The thickness of the adhesive layer formed from the water-based adhesive composition may be, for example, 5 μm or less, preferably 1 μm or less, more preferably 0.5 μm or less, and may be 0.01 μm or more, preferably 0.05 μm or more.
[0081] The thickness of the adhesive layer formed from the active energy ray-curable adhesive composition may be, for example, 10 μm or less, preferably 5 μm or less, more preferably 3 μm or less, and may be 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more.
[0082] (Liquid crystal coated linear polarizer)
[0083] A liquid crystal coating type linear polarizing plate as another example of the linear polarizing plate 32 includes an aligned cured product of a polymerizable liquid crystal compound and a dichroic dye, and the dichroic dye is dispersed and aligned in the cured product of the liquid crystal compound.
[0084] The thickness of the linear polarizing plate 32 in the case of a liquid crystal coating type is usually 10 μm or less, preferably 0.5 μm or more and 8 μm or less, and more preferably 1 μm or more and 5 μm or less.
[0085] Regarding polymerizable liquid crystal compounds, the polymerizable liquid crystal compounds described in the following phase difference layer items can be used. As polymerizable liquid crystal compounds used in polarizers, compared with nematic liquid crystal compounds, smectic liquid crystal compounds are preferred, and higher-order smectic liquid crystal compounds are more preferred. Among them, more preferred are higher-order smectic liquid crystal compounds that form smectic B phase, smectic D phase, smectic E phase, smectic F phase, smectic G phase, smectic H phase, smectic I phase, smectic J phase, smectic K phase or smectic L phase, and more preferably, higher-order smectic liquid crystal compounds that form smectic B phase, smectic F phase or smectic I phase. Photopolymerization initiators and the like can be appropriately used for polymerization.
[0086] A dichroic dye is a dye having a property that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction.
[0087] As a dichroic pigment, it is preferred that the dichroic pigment has an absorption maximum wavelength (λMAX) in the range of 300 to 700 nm. As such a dichroic pigment, for example, acridine pigments, oxazine pigments, cyanine pigments, naphthalene pigments, azo pigments and anthraquinone pigments can be cited, wherein azo pigments are preferred. As azo pigments, monoazo pigments, disazo pigments, triazo pigments, tetrazo pigments and stilbene azo pigments can be cited, preferably disazo pigments and triazo pigments. The dichroic pigment can be used alone or in combination, preferably in combination of 3 or more dichroic pigments, more preferably in combination of 3 or more azo pigments.
[0088] An example of a polarizing laminate (linear polarizing plate) 30 having a liquid crystal coating type polarizing plate as the linear polarizing plate 32 is shown in FIG. Figure 2 (c) and (d). Figure 2 In (c), the polarizing laminate (linear polarizing plate) 30 includes a first polarizer protective film 34, an orientation layer 33, a linear polarizer 32, and a second polarizer protective film 36 in this order. Figure 2 In (c), a second polarizer adhesive layer 39 for bonding the linear polarizer 32 and the second polarizer protective film 36 may be provided between the linear polarizer 32 and the second polarizer protective film 36. Examples and thicknesses of the polarizer adhesive layer are as described above.
[0089] exist Figure 2 In (d), the polarizing laminate (linear polarizing plate) 30 includes a first polarizer protective film 34, a linear polarizer 32, an orientation layer 33, and a second polarizer protective film 36 in this order. Figure 2 In (d), a first polarizer adhesive layer 38 may be provided between the linear polarizer 32 and the first polarizer protective film 34 to bond them together.
[0090] (Orientation layer 33 of liquid crystal coating type linear polarizer)
[0091] The orientation layer 33 is a layer for orienting the liquid crystal compound of the linear polarizer 32 when manufacturing the linear polarizer 32, and is in contact with the linear polarizer 32. The material of the orientation layer 33 is not particularly limited, and can be a friction layer of a resin such as PVA, or a light orientation layer that orients a polymer layer having a light orientation group by irradiating polarized light. The thickness of the orientation layer 33 is not limited, and the thickness of the orientation layer is usually in the range of 10 to 10000 nm, preferably in the range of 10 to 1000 nm, and more preferably in the range of 50 to 200 nm.
[0092] The materials of the alignment layer, polymerizable liquid crystal compound, and dichroic pigment are not particularly limited, and known materials can be used. Examples of these materials and methods of making them are disclosed in, for example, Japanese Patent Publication No. 2017-167517, Japanese Patent Publication No. 2013-37353, Japanese Patent Publication No. 2013-33249, Japanese Patent Publication No. 2017-83843, WO2020 / 122117, and WO2020 / 179864.
[0093] It should be noted that in the polarization laminate (linear polarization plate) 30, the Figure 2 After the alignment layer 33 on the linear polarizer 32 shown in (c) and (d) is attached to the first polarizer protective film 34 or the second polarizer protective film 36, in this case, for example, the polarization laminate (linear polarizing plate) 30 having a liquid crystal coating type polarizer as the linear polarizer 32 can be as follows Figure 2As in (a) and (b), the alignment layer 33 is not included.
[0094] (Polarizer protective film)
[0095] The polarizer protective film has the function of protecting the surface of the linear polarizer. The thickness of the first polarizer protective film 34 and the second polarizer protective film 36 is usually 10 to 100 μm. The first polarizer protective film 34 and the second polarizer protective film 36 can be the same type of material or different materials. In addition, the polarizer protective film can be a multi-layer laminate.
[0096] The first polarizer protective film 34 and the second polarizer protective film 36 may be made of resin films having excellent transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, stretchability, etc. The first polarizer protective film 34 and the second polarizer protective film 36 may be thermoplastic resin films. Specific examples of such thermoplastic resins include
[0097] Cellulose ester resins such as triacetyl cellulose;
[0098] Polyester resins such as polyethylene terephthalate and polyethylene naphthalate;
[0099] Polyethersulfone resin;
[0100] Polysulfone resin;
[0101] Polycarbonate resin;
[0102] Polyamide resins such as nylon and aromatic polyamide;
[0103] Polyimide resin;
[0104] Chain polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymer;
[0105] Cyclic polyolefin resins having a ring system and a norbornene structure (also called norbornene resins);
[0106] (Meth) acrylic resins such as polymethyl methacrylate;
[0107] Polyarylate resin;
[0108] Polystyrene resin;
[0109] Polyvinyl alcohol resin,
[0110] and mixtures thereof.
[0111] The protective film comprising the above-mentioned thermoplastic resin is commercially available.
[0112] Examples of the chain polyolefin-based resins include, in addition to homopolymers of chain olefins such as polyethylene resins (polyethylene resins as homopolymers of ethylene, copolymers mainly composed of ethylene) and polypropylene resins (polypropylene resins as homopolymers of propylene, copolymers mainly composed of propylene), copolymers containing two or more chain olefins.
[0113] Cyclic polyolefin resin is a general term for resins polymerized with cyclic olefin as a polymerization unit, and examples thereof include resins described in Japanese Patent Publication No. 1-240517, Japanese Patent Publication No. 3-14882, Japanese Patent Publication No. 3-122137, etc. If specific examples of cyclic polyolefin resins are given, they are ring-opening (co)polymers of cyclic olefins, addition polymers of cyclic olefins, copolymers of cyclic olefins with chain olefins such as ethylene and propylene (representatively, random copolymers), and graft polymers obtained by modifying them with unsaturated carboxylic acids and their derivatives, and their hydrogenated products. Among them, it is preferred to use a norbornene resin using a norbornene monomer such as norbornene and a polycyclic norbornene monomer as the cyclic olefin.
[0114] Polyester resins are resins having an ester bond in the main chain, and are generally polycondensates of polycarboxylic acids or their derivatives and polyols. As polycarboxylic acids or their derivatives, divalent dicarboxylic acids or their derivatives can be used, and examples thereof include terephthalic acid, isophthalic acid, dimethyl terephthalate, and dimethyl naphthalate. As polyols, divalent diols can be used, and examples thereof include ethylene glycol, propylene glycol, butanediol, neopentyl glycol, and cyclohexanedimethanol. As a representative example of polyester resins, polyethylene terephthalate, which is a polycondensate of terephthalic acid and ethylene glycol, can be cited.
[0115] Cellulose ester resins are esters of cellulose and fatty acids. Specific examples of cellulose ester resins include cellulose triacetate, cellulose diacetate, cellulose tripropionate, and cellulose dipropionate. In addition, copolymers having a plurality of polymerized units constituting these cellulose ester resins and polymers in which a portion of the hydroxyl groups is modified by other substituents can also be cited. Among them, cellulose triacetate (triacetyl cellulose) is particularly preferred.
[0116] (Meth)acrylic resins are resins whose main constituent monomers are compounds having (meth)acryloyl groups. Specific examples of (meth)acrylic resins include poly(meth)acrylates such as polymethyl methacrylate; methyl methacrylate-(meth)acrylic acid copolymers; methyl methacrylate-(meth)acrylic acid ester copolymers; methyl methacrylate-acrylate-(meth)acrylic acid copolymers; methyl (meth)acrylate-styrene copolymers (MS resins, etc.); copolymers of methyl methacrylate and compounds having alicyclic hydrocarbon groups (e.g. methyl methacrylate, cyclohexyl methacrylate copolymers, methyl methacrylate-(meth)acrylic acid norbornyl copolymers, etc.). It is preferred to use polymers having poly(meth)acrylic acid C1-C6 alkyl esters such as poly(meth)acrylate as the main component, and it is more preferred to use methyl methacrylate resins having methyl methacrylate as the main component (50 to 100% by mass, preferably 70 to 100% by mass).
[0117] The polycarbonate resin includes a polymer in which monomer units are bonded via a carbonate group. The polycarbonate resin may be a resin called a modified polycarbonate in which the polymer skeleton is modified, a copolymer polycarbonate, or the like.
[0118] The first polarizer protective film 34 and the second polarizer protective film 36 can be films formed by stretching a film containing the above-mentioned thermoplastic resin. As stretching treatment, uniaxial stretching, biaxial stretching, etc. can be cited. As stretching directions, the mechanical flow direction (MD) of the unstretched film, the direction (TD) orthogonal thereto, and the direction oblique to the mechanical flow direction (MD) can be cited. Biaxial stretching can be biaxial stretching while stretching in two stretching directions at the same time, or it can be a successive biaxial stretching in which stretching in other directions is performed after stretching in a specified direction. The stretching treatment can be performed, for example, as follows: using more than two pairs of clamping rollers with increased circumferential speeds on the outlet side, stretching along the length direction (mechanical flow direction: MD), or holding the two side ends of the unstretched film with a chuck and extending along the direction (TD) orthogonal to the mechanical flow direction. At this time, by adjusting the thickness of the film or adjusting the stretching ratio, the phase difference value and the wavelength dispersion value can be controlled. In addition, by adding a wavelength dispersion regulator to the resin, the wavelength dispersion value can be controlled.
[0119] The first polarizer protective film 34 and the second polarizer protective film 36 may contain any appropriate additives according to the purpose. As additives, for example, antioxidants such as hindered phenol, phosphorus, and sulfur, light stabilizers, ultraviolet absorbers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fiber and carbon fiber; near-infrared absorbers; flame retardants such as tris (dibromopropyl) phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic fillers, inorganic fillers; resin modifiers; plasticizers; lubricants; phase difference reducing agents, etc. The types, combinations, and contents of the additives contained can be appropriately set according to the purpose and the desired characteristics.
[0120] In addition, in order to impart the desired surface optical properties or other features, a coating layer (surface treatment layer) can be provided on the outer surface of the first polarizer protective film 34 and the second polarizer protective film 36. The specific example of the surface treatment layer includes a hard coat, an anti-glare layer, an anti-reflection layer, an antistatic layer, and an antifouling layer. The method for forming the surface treatment layer is not particularly limited, and a known method can be used. The surface treatment layer can be formed on one surface of each of the first polarizer protective film 34 and the second polarizer protective film 36, or can be formed on both surfaces respectively.
[0121] The hard coating layer has the function of improving the surface hardness of the first polarizer protective film 34 and the second polarizer protective film 36, and is provided for the purpose of preventing scratches on the surface. The hard coating layer is preferably a value H or harder than the pencil hardness measured by the pencil hardness test specified in JIS K 5600-5-4:1999 "General Test Methods for Coatings - Part 5: Mechanical Properties of Coatings - Section 4: Scratch Hardness (Pencil Method)" (a protective film having a hard coating layer is placed on a glass plate for measurement).
[0122] The material forming the hard coat layer is usually cured by heat or light. For example, organic hard coat materials such as silicone, melamine, epoxy, (meth) acrylic, and urethane (meth) acrylate, and inorganic hard coat materials such as silicon dioxide can be cited. Among them, urethane (meth) acrylate or multifunctional (meth) acrylate hard coat materials are preferably used from the aspects of good adhesion to the protective film and excellent productivity.
[0123] The hard coat layer may contain various fillers for the purpose of adjusting the refractive index, improving the bending elastic modulus, stabilizing the volume shrinkage, and improving heat resistance, antistatic properties, antiglare properties, etc. In addition, the hard coat layer may also contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, leveling agents, and defoaming agents.
[0124] In order to further improve the strength, the hard coating layer may contain additives. The additives are not limited, and inorganic particles, organic particles, or mixtures thereof may be cited. In addition, in order to have hardness, the thicker the hard coating layer, the better. However, if it is too thick, it is easy to break during cutting, so it can be 1 μm to 20 μm, or 2 μm to 10 μm. The thickness of the hard coating layer is preferably set to 3 μm to 7 μm.
[0125] The antiglare layer is a layer having fine concavo-convex shapes on the surface, and is preferably formed using the above-mentioned hard coating material.
[0126] The anti-glare layer having fine concavo-convex shapes on the surface can be formed by 1) forming a coating film containing microparticles on a protective film and providing concavo-convex shapes based on the microparticles; 2) forming a coating film containing microparticles or not containing microparticles on a protective film and then pressing it on a mold (roller, etc.) having a concavo-convex shape on the surface to transfer the concavo-convex shape (also called embossing method), etc.
[0127] The anti-reflection layer is a layer used to reduce the reflection of external light on the surface of the protective film for people observing the protective film, and the reflectivity of visible light is usually less than 1.5%. This anti-reflection layer with a reflectivity is typically formed by laminating a high refractive index layer with a high refractive index and a low refractive index layer with a low refractive index, or using the method and materials described in Japanese Patent Publication No. 2021-6929. By adjusting these refractive indices and the thickness of each layer, the reflected light from each layer can be mutually weakened, and an excellent anti-reflection function can be exerted.
[0128] The anti-reflection layer comprising a high refractive index layer and a low refractive index layer is described in detail later. If a coating composition capable of forming a high refractive index layer and a low refractive index layer is used to manufacture the anti-reflection layer, the operation is extremely simple, so it is preferred. Here, an example of a coating composition capable of forming a high refractive index layer and a low refractive index layer is listed. The coating composition is liquid and comprises a suitable curable resin and an additive as required. The coating composition capable of forming a high refractive index layer (composition for forming a high refractive index layer) is, for example, a curable resin such as urethane acrylate and an initiator (photopolymerization initiator) for photopolymerization such as acetophenone system, benzophenone system, benzyl dimethyl ketal system, α-hydroxyalkyl phenone system, α-aminoalkyl phenone system, thioxanthone system are dissolved in a solvent such as methyl ethyl ketone and methyl isobutyl ketone. In order to make the coating property better, a leveling agent, preferably a fluorine-based leveling agent, can be included. In addition, as a coating composition (low refractive index layer forming composition) capable of forming a low refractive index layer, silica particles are dispersed in a solution, wherein the solution is a binder resin such as polyethylene glycol diacrylate, pentaerythritol (tri / tetra) acrylate as a curable resin, and an initiator (photopolymerization initiator) for photopolymerization such as acetophenone, benzophenone, benzyl dimethyl ketal, α-hydroxyalkyl phenone, α-aminoalkyl phenone, thioxanthone are dissolved in a solvent such as 1-methoxy-2-propyl acetate and methyl isobutyl ketone. In order to make the coating property better, a fluorine-based leveling agent can be included. It should be noted that the coating composition capable of forming a high refractive index layer and a low refractive index layer respectively listed here is only an example, and it is preferred that the high refractive index layer forming composition and the low refractive index layer forming composition are optimized respectively according to the characteristics of the anti-reflection layer to be formed.
[0129] The antireflection layer may include, for example, a low refractive index layer. Alternatively, the antireflection layer may have a multilayer structure further including a high refractive index layer and / or a medium refractive index layer between the protective film and the low refractive index layer.
[0130] The low refractive index layer can be formed by applying a coating liquid containing a cured product of the above-mentioned curable resin, a light-transmitting resin such as a metal alkoxide polymer, and inorganic particles, and then curing the coating layer as needed. As inorganic particles, for example, low refractive particles such as LiF (refractive index 1.4), MgF (refractive index 1.4), 3NaF·AlF (refractive index 1.4), A1F (refractive index 1.4), Na3A1F6 (refractive index 1.33), hollow silica particles, etc. can be cited.
[0131] The antistatic layer is provided for the purpose of imparting conductivity to the surfaces of the first polarizer protective film 34 and the second polarizer protective film 36, suppressing the influence caused by static electricity, etc. The antistatic layer can be formed, for example, by coating a resin composition containing a conductive substance (antistatic agent) on the first protective film. For example, by making an antistatic agent coexist in the hard coating material for forming the hard coating, an antistatic hard coating can be formed.
[0132] The antifouling layer is provided to impart hydrophobicity, oleophobicity, sweat resistance, antifouling properties, etc. Suitable materials for forming the antifouling layer are fluorine-containing organic compounds. As fluorine-containing organic compounds, fluorocarbons, perfluorosilanes, and their polymer compounds, etc., can be cited. The method for forming the antifouling layer can use physical vapor deposition, chemical vapor deposition, wet coating, etc., with evaporation and sputtering as representative examples, depending on the material to be formed. The average thickness of the antifouling layer is usually about 1 to 50 nm, preferably 3 to 35 nm.
[0133] exist Figure 2 In (a) to (d), a protective film or a separator (these two may be referred to as a linear polarizing plate protective film (protective film)) 37 may be provided on the first polarizer protective film 34 preferably via a pressure-sensitive adhesive layer 35 .
[0134] (Protective membrane and diaphragm)
[0135] In order to prevent the surface of the polarizing laminate from being contaminated or damaged, the protective film and the diaphragm 37 are provided on the side of the polarizing laminate opposite to the side to which the phase element is bonded. The protective film may be attached to the first polarizing plate protective film 34 or the like by means of an adhesive layer 35, or may have self-adhesiveness and be attached to the first polarizing plate protective film 34 or the like alone. The diaphragm may be attached to the first polarizing plate protective film 34 or the like by means of an adhesive layer 35. The thickness of the protective film and the diaphragm may be, for example, 30 to 200 μm, preferably 30 to 150 μm, and more preferably 30 to 120 μm.
[0136] For example, after the circular polarizing plate with the protective film is attached to an image display element such as a liquid crystal cell or other optical components, the protective film is peeled off together with the adhesive layer attached to the protective film. On the other hand, for example, after the circular polarizing plate with the protective film is attached to an image display element such as a liquid crystal cell or other optical components, only the protective film is peeled off, and the adhesive layer attached to the protective film remains on the surface of the circular polarizing plate.
[0137] The protective film and the separator may contain an antistatic agent. The antistatic agent may be contained in the adhesive layer, for example. Alternatively, or in addition to the antistatic agent being contained in the adhesive layer, an antistatic layer containing the antistatic agent may be provided on the surface of the protective film and the separator opposite to the surface on which the adhesive layer is laminated.
[0138] Examples of the antistatic agent include ionic compounds. Ionic compounds are compounds having an inorganic cation or an organic cation and an inorganic anion or an organic anion. Two or more ionic compounds may be used.
[0139] The adhesion of the protective film and the diaphragm to the laminate at a temperature of 23°C and a relative humidity of 55% is preferably 0.01N / 25mm or more, 0.03N / 25mm or more, or 0.08N / 25mm or more. In addition, it is preferably 0.5N / 25mm or less, 0.4N / 25mm or less, or 0.3N / 25mm or less.
[0140] The above-mentioned adhesion can be measured by the following steps. The circular polarizing plate with a protective film and the circular polarizing plate with a diaphragm are cut into rectangles of any size, and the rectangles are attached to a glass substrate or the like to prepare test pieces. For the evaluation sample, a 180° peeling test is performed at a moving speed of 300 mm / min in accordance with JIS K6854-2:1999 "Adhesives - Peel Adhesion Strength Test Method - Part 2: 180° Peeling", and the measured peeling force is used as the adhesion.
[0141] When an adhesive layer is provided on the pellicle, the thickness of the adhesive layer is preferably 5 μm or more, 10 μm or more, or 15 μm or more, and preferably 30 μm or less, 25 μm or less, or 20 μm or less. The same applies to the adhesive layer of the separator.
[0142] Examples of the resin constituting the pellicle and the diaphragm include polyolefin resins such as polyethylene resins and polypropylene resins; cyclic polyolefin resins; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polycarbonate resins; (meth) acrylic resins, etc. Among them, polyester resins such as polyethylene terephthalate are preferred. The pellicle resin film may have a single-layer structure or a multilayer structure having two or more layers. The pellicle resin film may be a film subjected to a stretching treatment such as uniaxial stretching or biaxial stretching.
[0143] The pellicle membrane can be used by applying an adhesive on the pellicle surface and drying it to form an adhesive layer. The separator can be used by applying an adhesive on the separator resin film surface and drying it to form an adhesive layer.
[0144] The self-adhesive film that can be used as a pellicle is a film that is attached by itself without providing an adhesive layer or other attachment means and can maintain its attached state. The self-adhesive film can be formed using, for example, a polypropylene resin or a polyethylene resin.
[0145] The rigidity of the pellicle membrane can be 100,000 N / m to 500,000 N / m. The rigidity is the value obtained by multiplying the Young's modulus of the pellicle membrane by its thickness. The same applies to the rigidity of the diaphragm.
[0146] (Adhesive layer for protective film and diaphragm)
[0147] As the adhesive composition forming the adhesive layer, any adhesive composition with excellent optical transparency known in the past can be used without particular limitation, for example, an adhesive composition having a base polymer such as an acrylic resin, a urethane resin, a silicone resin, a polyvinyl ether resin, etc. can be used. In addition, an active energy ray-curable adhesive composition, a thermosetting adhesive composition, etc. can also be used. Among them, an adhesive composition having an acrylic resin as a base polymer that is excellent in transparency, adhesion, removability, weather resistance, heat resistance, etc. is suitable.
[0148] The adhesive composition may further include a cross-linking agent, a silane compound, an antistatic agent, and the like.
[0149] [(Meth)acrylic resin]
[0150] The (meth)acrylic resin contained in the adhesive composition is preferably a polymer (hereinafter also referred to as a "(meth)acrylate polymer") having a structural unit derived from an alkyl (meth)acrylate represented by the following formula (I) (hereinafter also referred to as "structural unit (I)") as a main component (for example, containing 50 parts by mass or more relative to 100 parts by mass of the structural unit of the (meth)acrylic resin).
[0151] In addition, in this specification, a (meth)acrylic resin may be either an acrylic resin or a methacrylic resin, and "(meth)" of (meth)acrylate etc. has the same meaning.
[0152] [Chemical formula 1]
[0153]
[0154] [Where R 10 represents a hydrogen atom or a methyl group, R 20 It represents an alkyl group having 1 to 20 carbon atoms, the alkyl group may have any structure of linear, branched or cyclic, and the hydrogen atoms of the alkyl group may be substituted by an alkoxy group having 1 to 10 carbon atoms.]
[0155] Examples of the (meth)acrylate represented by formula (I) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, stearyl (meth)acrylate, and tert-butyl (meth)acrylate. Specific examples of the alkyl acrylate containing an alkoxy group include 2-methoxyethyl (meth)acrylate and ethoxymethyl (meth)acrylate. Among them, it is preferable to contain n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate, and it is particularly preferable to contain n-butyl (meth)acrylate.
[0156] The (meth)acrylate polymer may contain structural units derived from other monomers in addition to the structural unit (I). The structural units derived from other monomers may be one or more. Other monomers that may be contained in the (meth)acrylate polymer include monomers having polar functional groups, monomers having aromatic groups, and acrylamide monomers.
[0157] Examples of the monomer having a polar functional group include (meth)acrylates having a polar functional group. Examples of the polar functional group include: hydroxyl groups; carboxyl groups; substituted or unsubstituted amino groups substituted with alkyl groups having 1 to 6 carbon atoms; heterocyclic groups such as epoxy groups, and the like.
[0158] The content of the structural unit derived from the monomer having a polar functional group in the (meth)acrylate polymer is preferably 10 parts by mass or less, more preferably 0.5 parts by mass or more and 10 parts by mass or less, further preferably 0.5 parts by mass or more and 5 parts by mass or less, particularly preferably 1 part by mass or more and 5 parts by mass or less, relative to 100 parts by mass of all structural units of the (meth)acrylate polymer.
[0159] Examples of monomers having an aromatic group include (meth)acrylates having one (meth)acryloyl group and one or more aromatic rings (e.g., benzene ring, naphthalene ring, etc.) in the molecule and having a phenyl group, a phenoxyethyl group, or a benzyl group. By including these structural units, the whitening phenomenon of the polarizing plate generated in a high temperature and high humidity environment can be suppressed.
[0160] The content of the structural unit derived from the monomer having an aromatic group in the (meth)acrylate polymer is preferably 20 parts by mass or less, more preferably 4 parts by mass or more and 20 parts by mass or less, and further preferably 4 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of all structural units of the (meth)acrylate polymer.
[0161] Examples of acrylamide monomers include N-(methoxymethyl)acrylamide, N-(ethoxymethyl)acrylamide, N-(propoxymethyl)acrylamide, N-(butoxymethyl)acrylamide, and N-(2-methylpropoxymethyl)acrylamide. By including these structural units, the bleeding of additives such as antistatic agents described below can be suppressed.
[0162] Furthermore, as structural units derived from other monomers other than the structural unit (I), structural units derived from styrene-based monomers, structural units derived from vinyl-based monomers, and structural units derived from monomers having a plurality of (meth)acryloyl groups in the molecule may be included.
[0163] The weight average molecular weight (hereinafter, also referred to as "Mw") of the (meth)acrylic resin (1) is preferably 500,000 to 2.5 million. If the weight average molecular weight is 500,000 or more, the durability of the first adhesive layer in a high temperature and high humidity environment can be improved. If the weight average molecular weight is 2.5 million or less, the operability when applying a coating liquid containing an adhesive composition becomes good. The molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight (Mw) to the number average molecular weight (hereinafter, also referred to as "Mn") is generally 2 to 10. In this specification, "weight average molecular weight" and "number average molecular weight" are polystyrene conversion values measured by gel permeation chromatography (GPC).
[0164] When the (meth)acrylic resin is dissolved in ethyl acetate to form a solution with a concentration of 20% by mass, the viscosity at 25°C is preferably 20 Pa·s or less, and more preferably 0.1 to 15 Pa·s. If the viscosity of the (meth)acrylic resin at 25°C is within the above range, it helps to improve the durability and reprocessability of the polarizing plate including the adhesive layer formed using the resin. The above viscosity can be measured by a Brookfield viscometer.
[0165] The glass transition temperature (Tg) of the (meth)acrylic resin is, for example, -60 to 20° C., preferably -50 to 15° C., more preferably -45 to 10° C., and further preferably -40 to 0° C. The glass transition temperature can be measured by a differential scanning calorimeter (DSC).
[0166] The (meth)acrylic resin may contain two or more (meth)acrylate polymers. Examples of such (meth)acrylate polymers include (meth)acrylate polymers having a relatively low molecular weight, such as a structural unit (I) derived from the above (meth)acrylate as a main component and a weight average molecular weight in the range of 50,000 to 300,000.
[0167] (Meth) acrylic resins can be generally produced by known polymerization methods such as solution polymerization, bulk polymerization, suspension polymerization, and emulsion polymerization. In the production of (meth) acrylic resins, polymerization is generally carried out in the presence of a polymerization initiator. The amount of the polymerization initiator used is generally 0.001 to 5 parts by mass relative to a total of 100 parts by mass of all monomers constituting the (meth) acrylic resin. (Meth) acrylic resins can also be produced by a method of polymerization using active energy rays such as ultraviolet rays.
[0168] [Crosslinking agent]
[0169] The adhesive composition preferably contains a crosslinking agent. As the crosslinking agent, conventional crosslinking agents (such as isocyanate compounds, epoxy compounds, aziridine compounds, metal chelate compounds, peroxides, etc.) can be cited, and isocyanate compounds are preferred from the viewpoints of the application period of the adhesive composition, the crosslinking speed, and the durability of the polarizing plate.
[0170] Isocyanate compounds are compounds having at least two isocyanate groups (-NCO) in the molecule. Specifically, toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, etc. can be mentioned. In addition, adducts obtained by reacting these isocyanate compounds with polyols such as glycerol and trimethylolpropane, dimers and trimers of these isocyanate compounds can also be mentioned. Two or more isocyanate compounds can be combined.
[0171] The ratio of the cross-linking agent relative to 100 parts by mass of the (meth)acrylic resin is, for example, 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 1 part by mass.
[0172] [Silane compounds]
[0173] The adhesive composition may further contain a silane compound.
[0174] Examples of the silane compound include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylethoxydimethylsilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane.
[0175] In addition, the silane compound may contain an oligomer derived from the above-mentioned silane compound.
[0176] The content of the silane compound in the adhesive composition is usually 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin. If the content of the silane compound is 0.01 parts by mass or more, there is a tendency for the adhesion between the adhesive layer and the adherend to be improved, and if the content is 10 parts by mass or less, there is a tendency for the oozing out of the silane compound from the adhesive layer to be suppressed.
[0177] <Antistatic Agent>
[0178] The adhesive composition may further include an antistatic agent. As the antistatic agent, known antistatic agents can be cited, and ionic antistatic agents are suitable. As cationic components constituting the ionic antistatic agent, organic cations and inorganic cations can be cited. As organic cations, pyridinium cations, imidazolium cations, ammonium cations, sulfonium cations, phosphonium cations, etc. can be cited. As inorganic cations, alkali metal cations such as lithium cations, potassium cations, sodium cations, and cesium cations, alkaline earth metal cations such as magnesium cations and calcium cations can be cited. As an anionic component constituting the ionic antistatic agent, it can be any one of an inorganic anion and an organic anion. From the aspect of excellent antistatic performance, an anionic component containing fluorine atoms is preferably used. As an anionic component containing fluorine atoms, hexafluorophosphate anion (PF6-), bis(trifluoromethanesulfonyl)imide anion [(CF3SO2)2N - ]、bis(fluorosulfonyl)imide anion [(FSO2)2N - ] anions, etc.
[0179] From the viewpoint of excellent temporal stability of the antistatic performance of the pressure-sensitive adhesive composition, an ionic antistatic agent that is solid at room temperature is preferred.
[0180] The content of the antistatic agent is, for example, 0.01 to 20 parts by mass, preferably 0.1 to 10 parts by mass, and more preferably 1 to 7 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin.
[0181] The adhesive composition may contain additives such as ultraviolet absorbers, solvents, crosslinking catalysts, tackifying resins (tackifiers), plasticizers, etc., alone or in combination of two or more thereof. In addition, it is also useful to prepare a harder adhesive layer by adding an ultraviolet curable compound to the adhesive composition and curing it by irradiating ultraviolet rays after forming the adhesive layer.
[0182] The adhesive layer can be formed, for example, by dissolving or dispersing the adhesive composition in a solvent to prepare an adhesive composition containing a solvent, and then applying the solvent composition to the surface of the layer where the adhesive layer is to be provided and drying the composition.
[0183] The thickness of the pressure-sensitive adhesive layer is usually 0.1 to 30 μm, preferably 3 to 30 μm, and more preferably 5 to 25 μm.
[0184] Figure 2 The polarizing laminate (linear polarizing plate) 30 of (b) is formed from Figure 2 The polarizing laminate 30 of (a) is a polarizing laminate in which the second polarizer adhesive layer 39 and the second polarizer protective film 36 are removed, but the polarizing laminate (linear polarizing plate) may also be a polarizing laminate (linear polarizing plate) Figure 2 The polarizing laminate 30 of (a) is a polarizing laminate in which the first polarizer adhesive layer 38 and the first polarizer protective film 34 are removed.
[0185] (Polarizing laminate including liquid crystal retardation layer)
[0186] The polarizing laminate 30 may further include a liquid crystal retardation layer via a bonding adhesive layer, preferably a layer of an active energy ray-curable adhesive. The liquid crystal retardation layer is preferably laminated on the side closer to the phase element 50 than the linear polarizing plate.
[0187] For example, in Figure 3 In (a) and (c), the polarizing laminate 30 includes a pressure-sensitive adhesive layer 71 and a liquid crystal retardation layer 72 in this order below the second polarizer protective film 36 .
[0188] exist Figure 3 In (b) and (d), the polarizing laminate 30 has a pressure-sensitive adhesive layer 71 and a liquid crystal retardation layer 72 in this order below the linear polarizing plate 32 .
[0189] The material, thickness, and method of manufacture of the liquid crystal phase difference layer can be set in the same manner as described later in the description of the phase element. The material, thickness, and method of manufacture of the adhesive are not particularly limited, and may be, for example, the material, thickness, and method exemplified in the polarizer adhesive layer, the material, thickness, and method exemplified in the adhesive layer of the protective film, and the material, thickness, and method exemplified in the layer 40 of the active energy ray-curable adhesive.
[0190] In this specification, the protective film in the polarizing stack 30 refers to a film other than the linear polarizer and having a rigidity of 20000 N / m or more, which can help suppress deformation of the polarizing stack 30. In this specification, the rigidity of the film is defined by the longitudinal elastic coefficient (Young's modulus) of the film × thickness.
[0191] Specifically, the protective film in the polarizing stack 30 may be a polarizer protective film; a coating layer such as a hard coat layer, an anti-glare layer, an anti-reflection layer, an antistatic layer, an anti-fouling layer, or a protective film; or a diaphragm.
[0192] Generally, polarizing plate adhesive layers, tackiness adhesive layers, liquid crystal retardation layers, alignment layers, etc. have low rigidity and therefore do not correspond to protective films.
[0193] In the present embodiment, the total rigidity value of each protective film in the polarizing laminate 30 is 250,000 N / m or less.
[0194] To this end, the number of protective films, and their Young's modulus and thickness may be appropriately adjusted.
[0195] (Active Energy Ray-Curing Adhesive Layer 40)
[0196] The active energy ray-curable adhesive layer 40 is disposed between the polarizing laminate 30 and the phase element 50 and is in contact with these.
[0197] The shear stress α of the cured product of the active energy ray-curable adhesive at 25° C. is not more than 100 Pa. The material of the active energy ray-curable adhesive is not particularly limited.
[0198] In this specification, the shear stress α refers to the maximum stress when a cured product of an active energy ray-curable adhesive in the shape of a disk with a diameter of 8 mm and a thickness of 5 μm is clamped between a pair of parallel plates and vibrated about the central axis of the disk at a rotation angle of 1 mrad and a frequency of 1 Hz to apply a torsional moment.
[0199] Such shear stress α can be measured using a viscoelasticity measuring device (MCR-301, Anton Paar) or the like.
[0200] The curing conditions were set to use a xenon halogen lamp at 30 mW / cm 2 Expose to UVA for 30 seconds.
[0201] (Active energy ray-curable adhesive)
[0202] One form of an active energy ray-curable adhesive is an adhesive that is cured by irradiating active energy rays. The active energy ray-curable adhesive contains a curable component and a cationic polymerization initiator (D). The curable component contains a polyfunctional aromatic epoxy compound (A), and may also contain an alicyclic epoxy compound (B) or a monofunctional epoxy compound (C). For the curable component in the active energy ray-curable adhesive, when the total amount of the curable component is set to 100 parts by mass,
[0203] As the polyfunctional aromatic epoxy compound (A), 10 to 90 parts by mass, preferably 30 to 75 parts by mass of a polyfunctional aromatic epoxy compound having a viscosity of 30 Pa·s or less at a temperature of 25° C. is contained.
[0204] The alicyclic epoxy compound (B) contains less than 25 parts by mass, for example, 1 to 22 parts by mass,
[0205] It is suitable to contain less than 20 parts by mass, for example 1 to 18 parts by mass of the monofunctional epoxy compound (C).
[0206] The curable component may include compounds other than the polyfunctional aromatic epoxy compound (A), the alicyclic epoxy compound (B) and the monofunctional epoxy compound (C), and may also include a polyfunctional aliphatic epoxy compound (E) and an oxetane compound (F). For the curable component in the active energy ray-curable adhesive, when the total amount of the curable component is 100 parts by mass,
[0207] For example, 1 to 50 parts by mass of a polyfunctional aliphatic epoxy compound (E) may be contained.
[0208] For example, the oxetane compound (F) is contained in an amount of 1 to 50 parts by mass.
[0209] The active energy ray-curable adhesive preferably does not contain a solvent.
[0210] (1) Curing component
[0211] (Polyfunctional aromatic epoxy compound (A))
[0212] The polyfunctional aromatic epoxy compound (A) is a compound having two or more epoxy groups and an aromatic ring. However, the polyfunctional aromatic epoxy compound (A) mentioned in this specification does not include a compound having an alicyclic epoxy group in the molecule contained in the alicyclic epoxy compound (B). The alicyclic epoxy group will be described later.
[0213] Specific examples of the polyfunctional aromatic epoxy compound (A) include polyglycidyl ethers of naphthalene or naphthalene derivatives (also referred to as "naphthalene-type epoxy compounds"); polyglycidyl ethers of bisphenol derivatives such as bisphenol A and bisphenol F (also referred to as "bisphenol A-type epoxy compounds" and "bisphenol F-type epoxy compounds"); epoxy novolac resins; polyglycidyl ethers of aromatic compounds having two or more phenolic hydroxyl groups such as resorcinol, hydroquinone, and catechol; polyglycidyl ethers of aromatic compounds having two or more alcoholic hydroxyl groups such as benzyl alcohol, benzyl alcohol, and benzyl butanol; polyglycidyl esters of polyacid aromatic compounds having two or more carboxyl groups such as phthalic acid, terephthalic acid, and trimellitic acid; glycidyl esters of benzoic acid, toluic acid, and naphthoic acid; styrene oxides such as styrene oxide, alkylated styrene oxide, and epoxides of vinyl naphthalene, or diepoxides of divinylbenzene, etc.
[0214] When the total amount is 100 parts by mass, the curable component of the active energy ray-curable adhesive of the present invention contains 10 to 90 parts by mass, preferably 30 to 75 parts by mass of a polyfunctional aromatic epoxy compound having a viscosity of 30 Pa·s or less at a temperature of 25° C. as the polyfunctional aromatic epoxy compound (A). By using a polyfunctional aromatic epoxy compound having a viscosity of 30 Pa·s or less at a temperature of 25° C. as the polyfunctional aromatic epoxy compound (A), the viscosity of the active energy ray-curable adhesive can be reduced. In addition, the refractive index of the layer of the cured product of the adhesive can be increased, the adhesiveness can be improved, and wrinkles generated in the optical laminate when bent can be suppressed.
[0215] As the polyfunctional aromatic epoxy compound having a viscosity of 30 Pa·s or less at a temperature of 25° C., commercially available products can be used, for example, “DENACOL EX-201”, “DENACOL EX-711” and “DENACOL EX-721” (all manufactured by Nagase ChemteX Co., Ltd.); “OGSOL EG-280” and “OGSOL CG-400” (all manufactured by Osaka Gas Chemical Co., Ltd.); “EXA-80CRP” and “HP4032D” (all manufactured by DIC Corporation); “jER828” and “jER828EL” (all manufactured by Mitsubishi Chemical Corporation); “ADEKA RESIN EP-4100”, “ADEKA RESIN EP-4100G”, “ADEKA RESIN EP-4100E”, “ADEKA RESIN EP-4100L”, “ADEKA RESIN EP-4100TX", "ADEKARESIN EP-4000", "ADEKA RESIN EP-4005", "ADEKA RESIN EP-4901", "ADEKA RESIN EP-4901E" (the above are all manufactured by ADEKA Co., Ltd.), etc.
[0216] As the polyfunctional aromatic epoxy compound having a viscosity of 30 Pa·s or less at a temperature of 25° C., one kind of compound may be used alone, or a plurality of different kinds may be used in combination.
[0217] (Alicyclic epoxide compound (B))
[0218] The alicyclic epoxy compound (B) is a compound having one or more alicyclic epoxy groups. As long as the alicyclic epoxy compound (B) is a compound having one or more alicyclic epoxy groups, it may further have an epoxy group other than the alicyclic epoxy group. In this specification, the alicyclic epoxy group refers to an epoxy group bonded to an alicyclic ring, and refers to the bridging oxygen atom -O- in the structure shown in the following formula (a).
[0219] [Chemical formula 2]
[0220]
[0221] In the above formula (a), m is an integer of 2 to 5. The above formula (a) without (CH2) m The compound formed by the group after one or more hydrogen atoms in the (CH2) and other chemical structures can become an alicyclic epoxy compound (B). mOne or more hydrogen atoms in the alicyclic epoxy compound (B) may be appropriately substituted with a linear alkyl group such as a methyl group or an ethyl group. The alicyclic epoxy compound (B) can adjust the curing speed of the active energy ray-curable adhesive and can also provide a cured adhesive layer having good high temperature resistance.
[0222] Specific examples of the alicyclic epoxy compound (B) include 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-1-methyl-4-(1-methylepoxyethyl)cyclohexane, 3,4-epoxycyclohexylmethyl methacrylate, 4-(1,2-epoxyethyl)-1,2-epoxycyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol, ethylenebis(3,4-epoxycyclohexanecarboxylate), oxydiethylenebis(3,4-epoxycyclohexanecarboxylate), 1,4-cyclohexanedimethylbis(3,4-epoxycyclohexanecarboxylate), and 3-(3,4-epoxycyclohexylmethoxycarbonyl)propyl 3,4-epoxycyclohexanecarboxylate.
[0223] Among the alicyclic epoxy compounds (B), 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate is preferably used because it has moderate curability and can be obtained at a relatively low cost. As the alicyclic epoxy compound (B), one alicyclic epoxy compound may be used alone or in combination of different alicyclic epoxy compounds.
[0224] The alicyclic epoxy compound (B) can be a commercially available product. For example, each of the products is represented by a trade name, and examples thereof include "CELLOXIDE (registered trademark)" series and "CYCLOMER (registered trademark)" sold by Daicel Co., Ltd. and "CYRACURE UVR" series sold by Dow Chemical.
[0225] (Monofunctional epoxy compound (C))
[0226] The monofunctional epoxy compound (C) is a compound having one epoxy group. However, the monofunctional epoxy compound (C) mentioned in this specification does not include a compound having an alicyclic epoxy group in the molecule contained in the alicyclic epoxy compound (B). The monofunctional epoxy compound (C) may or may not have an aromatic ring in the molecule. The monofunctional epoxy compound (C) can be used to adjust the viscosity of the active energy ray-curable adhesive.
[0227] Examples of the monofunctional epoxy compound (C) having an aromatic ring include monoglycidyl ethers of monophenols such as phenol, cresol, and butylphenol, or bisphenol derivatives such as bisphenol A and bisphenol F, or their alkylene oxide adducts; epoxy novolac resins; monoglycidyl ethers of aromatic compounds having two or more phenolic hydroxyl groups such as resorcinol, hydroquinone, and catechol; monoglycidyl ethers of aromatic compounds having two or more alcoholic hydroxyl groups such as benzyl alcohol, benzyl alcohol, and benzyl butanol; monoglycidyl esters of polyacid aromatic compounds having two or more carboxyl groups such as phthalic acid, terephthalic acid, and trimellitic acid; glycidyl esters of benzoic acid, monoglycidyl esters of toluic acid, and monoglycidyl esters of naphthoic acid; and the like.
[0228] As the monofunctional epoxy compound (C) having no aromatic ring, there can be mentioned glycidyl ethers of aliphatic alcohols, glycidyl esters of alkyl carboxylic acids, etc., and specific examples thereof include allyl glycidyl ether, butyl glycidyl ether, sec-butylphenyl glycidyl ether, 2-ethylhexyl glycidyl ether, mixed alkyl glycidyl ethers having 12 and 13 carbon atoms, glycidyl ethers of alcohols, monoglycidyl ethers of aliphatic higher alcohols, glycidyl esters of higher fatty acids, etc. As the monofunctional epoxy compound (C), one type of monofunctional epoxy compound may be used alone, or different types of monofunctional epoxy compounds may be used in combination.
[0229] As the monofunctional epoxy compound (C), a commercially available product can be used, and examples thereof include "EX-142", "EX-146", "EX-147", and "EX-121" (all of which are manufactured by Nagase ChemteX Corporation).
[0230] (Multifunctional aliphatic epoxy compound (E))
[0231] The polyfunctional aliphatic epoxy compound (E) is a compound having two or more epoxy groups and no aromatic ring. The polyfunctional aliphatic epoxy compound (E) mentioned in this specification does not include a compound having an alicyclic epoxy group contained in the alicyclic epoxy compound (B). The polyfunctional aliphatic epoxy compound (E) can adjust the adhesiveness of the cured layer of the adhesive.
[0232] As the polyfunctional aliphatic epoxy compound (E), an aliphatic diepoxy compound represented by the following formula (I) is more preferred. By including the aliphatic diepoxy compound represented by the following formula (I) as the polyfunctional aliphatic epoxy compound (E), an active energy ray-curable adhesive having low viscosity and easy coating can be obtained.
[0233] [Chemical formula 3]
[0234]
[0235] In formula (I), Z is an alkylene group having 1 to 9 carbon atoms, an alkylidene group having 3 or 4 carbon atoms, a divalent alicyclic hydrocarbon group, or a group of the formula -C m H 2m -Z 1 -C n H 2n - is a divalent group. m H 2m -Z 1 -C n H 2n -Z 1 - is -O-, -CO-O-, -O-CO-, -SO2-, -SO- or -CO-, m and n each independently represent an integer greater than 1, and the total of m and n is 9 or less.
[0236] The divalent alicyclic hydrocarbon group may be, for example, a divalent alicyclic hydrocarbon group having 4 to 8 carbon atoms, and examples thereof include a divalent group represented by the following formula (I-1).
[0237] [Chemical formula 4]
[0238]
[0239] Specific examples of the compound represented by formula (I) include diglycidyl ethers of alkanediols, diglycidyl ethers of oligoalkylene glycols having a repeating number of up to about 4, and diglycidyl ethers of alicyclic diols.
[0240] Examples of glycols that can form the compound represented by the above formula (I) include ethylene glycol, propylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-2,4-pentanediol, 2,4-pentanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, Alkanediol such as diol, 2-methyl-2,4-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 3,5-heptanediol, 1,8-octanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol; oligoalkylene glycol such as diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol; alicyclic diols such as cyclohexanediol and cyclohexanedimethanol.
[0241] In the present invention, as the polyfunctional aliphatic epoxy compound (E), 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and neopentyl glycol diglycidyl ether are preferred from the viewpoint of obtaining an active energy ray-curable adhesive having low viscosity and being easy to apply. As the polyfunctional aliphatic epoxy compound (E), one aliphatic epoxy compound may be used alone, or a plurality of different aliphatic epoxy compounds may be used in combination.
[0242] As the polyfunctional aliphatic epoxy compound (E), commercially available products may be used, and examples thereof include "EP-4088S" (both manufactured by ADEKA Corporation), "EHPE3150" (both manufactured by Daicel Corporation), "EX-211L" and "EX-212L" (both manufactured by Nagase ChemteX Corporation).
[0243] (Oxetane compound (F))
[0244] In this specification, the oxetane compound (F) is a compound having an oxetane group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound. The oxetane compound (F) mentioned in this specification is a compound not having an epoxy group. The oxetane compound (F) can be used to adjust the curing speed and viscosity of the active energy ray-curable adhesive, and can also improve reactivity.
[0245] Specific examples of the oxetane compound (F) include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, Tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,4-bis(3-ethyl-3-oxetanylmethoxy)butane, 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-[(phenoxy)methyl]oxetane, 3-ethyl-3-(hexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-(hydroxymethyl)oxetane, 3-ethyl-3-(chloromethyl)oxetane, etc. As the oxetane compound (F), one oxetane compound may be used alone, or different oxetane compounds may be used in combination.
[0246] The oxetane compound (F) may be a commercially available product, and examples thereof include "Aron Oxetane (registered trademark)" series sold by Toagosei Co., Ltd. and "ETERNACOLL (registered trademark)" series sold by Ube Industries, Ltd.
[0247] In order to make the active energy ray-curable adhesive solvent-free, the above-mentioned curable components (polyfunctional epoxy compound (A), alicyclic epoxy compound (B), monofunctional epoxy compound (C), polyfunctional aliphatic epoxy compound (E), oxetane compound (F)) are preferably used without being diluted with an organic solvent or the like.
[0248] The curable component is usually liquid at room temperature, has appropriate fluidity even in the absence of a solvent, and has a suitable bonding strength. The active energy ray-curable adhesive with a cationic polymerization initiator suitable for the curable component can omit the drying equipment for evaporating the solvent in the process of bonding the first optical layer and the second optical layer in the manufacturing equipment of the optical laminate. In addition, by irradiating an appropriate amount of active energy rays, the curing speed can be accelerated and the production speed can be increased.
[0249] (Other curing ingredients)
[0250] The curable component contained in the active energy ray-curable adhesive is not limited to the above-mentioned curable components, and may include a cationically polymerizable curable component other than the above-mentioned cationically polymerizable curable component and a radically polymerizable curable component. Examples of the radically polymerizable curable component include acrylic compounds.
[0251] However, since radical polymerization tends to cause large shrinkage during curing, the active energy ray-curable adhesive preferably contains only a cationically polymerizable curable component as a curable component.
[0252] (2) Cationic polymerization initiator (D)
[0253] The active energy ray-curable adhesive contains a cationic polymerization initiator (D). Thus, the curable component can be cured by cationic polymerization based on the irradiation of active energy rays to form an adhesive layer. The cationic polymerization initiator (D) generates cationic species or Lewis acids by irradiation of active energy rays such as visible light, ultraviolet rays, X-rays, and electron beams, and initiates the polymerization reaction of the curable component. The cationic polymerization initiator (D) acts as a catalyst through light, so even if it is mixed into the curable component, the storage stability and workability are excellent. As a compound that can be used as a cationic polymerization initiator (D) and generates cationic species and Lewis acids by irradiation of active energy rays, for example, aromatic diazonium salts; aromatic iodonium salts, aromatic sulfonium salts and the like; iron-arene complexes, etc.
[0254] Examples of the aromatic diazonium salt include benzenediazonium hexafluoroantimonate, benzenediazonium hexafluorophosphate, and benzenediazonium hexafluoroborate.
[0255] Examples of the aromatic iodonium salt include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and di(4-nonylphenyl)iodonium hexafluorophosphate.
[0256] Examples of the aromatic sulfonium salt include triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, 4,4'-bis[diphenylsulfonyl]diphenyl sulfide bishexafluorophosphate, 4,4'-bis[bis(β-hydroxyethoxy)phenylsulfonyl]diphenyl sulfide bishexafluoroantimonate, 4,4'-bis[bis(β-hydroxyethoxy)phenylsulfonyl]diphenyl sulfide bishexafluorophosphate, 7-[di(p-toluoyl)sulfonyl] 〕-2-isopropylthioxanthone hexafluoroantimonate, 7-〔di(p-toluoyl)sulfonium〕-2-isopropylthioxanthone tetrakis(pentafluorophenyl)borate, 4-phenylcarbonyl-4'-diphenylsulfonium-diphenyl sulfide hexafluorophosphate, 4-(p-tert-butylphenylcarbonyl)-4'-diphenylsulfonium-diphenyl sulfide hexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4'-di(p-toluoyl)sulfonium-diphenyl sulfide tetrakis(pentafluorophenyl)borate.
[0257] Examples of the iron-arene complex include xylene-cyclopentadienyl iron (II) hexafluoroantimonate, cumene-cyclopentadienyl iron (II) hexafluorophosphate, and xylene-cyclopentadienyl iron (II) tris(trifluoromethanesulfonyl)methanide.
[0258] Cationic polymerization initiator (D) can be used alone or in combination of two or more. Among the above, aromatic sulfonium salts have ultraviolet absorption characteristics even in the wavelength region near 300nm, so they are excellent in curability and can obtain a cured layer of an adhesive with good mechanical strength and bonding strength, so they are preferably used.
[0259] The content of the cationic polymerization initiator (D) is set to 0.5 to 10 parts by mass, preferably 1 to 4 parts by mass, relative to 100 parts by mass of the total amount of the curable components. By containing more than 1 part by mass of the cationic polymerization initiator (D), the curable components can be fully cured, and a layer of a cured product of an adhesive having sufficient bonding strength and hardness can be obtained. On the other hand, if the amount becomes more, the ionic substances in the cured product increase, the hygroscopicity of the cured product becomes higher, and it is possible to reduce the durability of the optical laminate, so the amount of the cationic polymerization initiator (D) is set to less than 10 parts by mass relative to 100 parts by mass of the total amount of the curable components.
[0260] When a radical polymerizable curable component is contained as the curable component, it is preferred that a radical polymerization initiator is contained as the polymerization initiator in addition to the cationic polymerization initiator (D).
[0261] (3) Photosensitizer
[0262] The active energy ray curing adhesive may contain a photosensitizer. The cationic polymerization initiator (D) exhibits maximum absorption near 300 nm or in a wavelength region shorter than that, senses light of a wavelength near that and generates cationic species or Lewis acid, and initiates cationic polymerization of a cationic polymerizable curable component. In order to also sense light of a wavelength longer than that, the photosensitizer preferably exhibits maximum absorption in a wavelength region longer than 380 nm. As the photosensitizer, anthracene compounds are preferably used.
[0263] Specific examples of anthracene compounds include:
[0264] 9,10-Dimethoxyanthracene,
[0265] 9,10-diethoxyanthracene,
[0266] 9,10-Dipropoxyanthracene,
[0267] 9,10-diisopropoxyanthracene,
[0268] 9,10-dibutoxyanthracene,
[0269] 9,10-dipentyloxyanthracene,
[0270] 9,10-Dihexyloxyanthracene,
[0271] 9,10-Bis(2-methoxyethoxy)anthracene,
[0272] 9,10-Bis(2-ethoxyethoxy)anthracene,
[0273] 9,10-bis(2-butoxyethoxy)anthracene,
[0274] 9, 10. Bis(3-butoxypropoxy)anthracene,
[0275] 2-methyl or 2-ethyl-9,10-dimethoxyanthracene,
[0276] 2-methyl or 2-ethyl-9,10-diethoxyanthracene,
[0277] 2-methyl or 2-ethyl-9,10-dipropoxyanthracene,
[0278] 2-methyl or 2-ethyl-9,10-diisopropoxyanthracene,
[0279] 2-methyl or 2-ethyl-9,10-dibutoxyanthracene,
[0280] 2-methyl or 2-ethyl-9,10-dipentyloxyanthracene,
[0281] 2-Methyl or 2-ethyl-9,10-dihexyloxyanthracene.
[0282] By including a photosensitizer in the active energy ray-curable adhesive, the curability of the adhesive can be improved compared to the case where the photosensitizer is not included. Such an effect can be exhibited by making the content of the photosensitizer 0.1 mass parts or more relative to 100 mass parts of the total amount of the curable components. On the other hand, if the content of the photosensitizer increases, problems such as precipitation during low-temperature storage occur, so its content is preferably set to 2 mass parts or less relative to 100 mass parts of the total amount of the curable components.
[0283] (4) Photosensitizing agent
[0284] The active energy ray-curable adhesive may contain a photosensitizer, which is preferably a naphthalene-based photosensitizer.
[0285] Specific examples of the naphthalene-based photosensitizing aid include 4-methoxy-1-naphthol, 4-ethoxy-1-naphthol, 4-propoxy-1-naphthol, 4-butoxy-1-naphthol, 4-hexyloxy-1-naphthol, 1,4-dimethoxynaphthalene, 1-ethoxy-4-methoxynaphthalene, 1,4-diethoxynaphthalene, 1,4-dipropoxynaphthalene, and 1,4-dibutoxynaphthalene.
[0286] By making the active energy ray curing type adhesive contain a naphthalene-based photosensitizing aid, the curability of the adhesive can be improved compared with the case where the naphthalene-based photosensitizing aid is not contained. By making the content of the naphthalene-based photosensitizing aid be 0.1 mass parts or more relative to 100 mass parts of the total amount of curable components, such an effect can be shown. On the other hand, if the content of the naphthalene-based photosensitizing aid becomes more, problems such as precipitation during low temperature storage are generated, and therefore, its content is preferably less than 5 mass parts relative to 100 mass parts of the total amount of curable components. The content of the naphthalene-based photosensitizing aid is preferably less than 3 mass parts relative to 100 mass parts of the total amount of curable components.
[0287] (5) Additive ingredients
[0288] The active energy ray-curable adhesive may contain additive components as other components of the optional components as long as the effects of the present invention are not impaired. Examples of additive components include ion trapping agents, antioxidants, light stabilizers, chain transfer agents, tackifiers, thermoplastic resins, fillers, flow regulators, plasticizers, defoamers, leveling agents, pigments, organic solvents, and the like.
[0289] When an additive component is contained, its content is preferably 10 parts by mass or less relative to 100 parts by mass of the total amount of the curable component. When the content is 10 parts by mass or less, the excellent bonding strength between the first optical layer and the second optical layer, the low viscosity of the active energy ray-curable adhesive and the good coating properties thereof, and the effect of suppressing bubble defects in the first adhesive layer after curing can be well exerted.
[0290] The cationic polymerization initiator (D), photosensitizer, photosensitizer aid and additive components can be added in a solvent-free state when preparing the active energy ray-curable adhesive, or can be added directly after being diluted in a solvent. The numerical ranges of the above contents are all numerical ranges based on the solid content.
[0291] The thickness of the active energy ray-curable adhesive layer 40 is not particularly limited, and may be, for example, 0.1 μm or more, 0.5 μm or more, or 10 μm or less, 5 μm or less, or 3 μm or less.
[0292] (Phase element 50)
[0293] The phase element 50 is an optical element including one or more liquid crystal phase difference layers, and exhibits a phase difference in a plane or in a thickness direction. The liquid crystal phase difference layer is a layer of a cured product of a polymerizable liquid crystal compound.
[0294] (Liquid crystal phase difference layer)
[0295] like Figure 4 As shown in (a), the phase element 50 may have a first liquid crystal phase difference layer 52 and an orientation layer 54 connected to the first liquid crystal phase difference layer 52. The orientation layer 54 can be connected to the substrate layer 80. The phase element 50 may not have an orientation layer. In order to highly realize the anti-reflection function, the phase element 50 preferably has a liquid crystal phase difference layer, and the liquid crystal phase difference layer has a λ / 4 plate function in the entire visible light region (i.e., a phase difference function of π / 2). For example, the first liquid crystal phase difference layer 52 of the phase element 50 may have a phase difference layer having a λ / 4 plate function with reverse wavelength dispersion.
[0296] The phase element 50 may include a plurality of liquid crystal phase difference layers. Figure 4 As shown in (b), the phase element 50 of one embodiment includes a second liquid crystal phase difference layer 58, a phase element adhesive layer 56, a first liquid crystal phase difference layer 52, and an alignment layer 54, and the alignment layer 54 is in contact with the base layer 80. The alignment layer 54 is not essential.
[0297] The plurality of liquid crystal phase difference layers may be liquid crystal phase difference layers having different optical anisotropies, for example, liquid crystal phase difference layers having different orientation directions. For example, the phase element 50 may also have a liquid crystal phase difference layer having a λ / 2 plate function (i.e., a phase difference function of π) and a liquid crystal phase difference layer having a λ / 4 plate function (i.e., a phase difference function of π / 2).
[0298] In order to compensate for the antireflection function in the oblique direction, the phase element 50 may further include a liquid crystal phase difference layer (positive C plate) having anisotropy in the thickness direction. Each liquid crystal phase difference layer may be in an oblique orientation or a cholesteric orientation state.
[0299] The value of wavelength dispersion α of the phase element is preferably within a specified range. Here, "wavelength dispersion α" refers to the ratio of the in-plane phase difference value Re(450) at a wavelength of 450nm to the in-plane phase difference value Re(550) at a wavelength of 550nm (Re(450) / Re(550)). From the perspective of improving the reverse wavelength dispersion and further improving the optical properties of the liquid crystal phase difference layer, the value of wavelength dispersion α is preferably greater than 0.70, and more preferably greater than 0.78. In addition, for the same reason, wavelength dispersion α is preferably less than 0.92, more preferably less than 0.90, further preferably less than 0.88, and particularly preferably less than 0.87.
[0300] When the in-plane phase difference value relative to light of wavelength λnm is set to Re(λ), the λ / 4 function in the entire visible light region preferably satisfies the optical characteristics shown in the following formula (1), and preferably satisfies the optical characteristics shown in the following formula (1), the following formula (2) and the following formula (3).
[0301] 100nm<Re(550)<160nm (1)
[0302] (Wherein, Re(550) represents the in-plane phase difference value (in-plane retardation) with respect to light of wavelength 550 nm.)
[0303] Re(450) / Re(550)≤1.0 (2)
[0304] 1.00≤Re(650) / Re(550) (3)
[0305] (Wherein, Re(450) represents the in-plane phase difference value relative to light with a wavelength of 450 nm, Re(550) represents the in-plane phase difference value relative to light with a wavelength of 550 nm, and Re(650) represents the in-plane phase difference value relative to light with a wavelength of 650 nm.)
[0306] The in-plane phase difference value of the liquid crystal phase difference layer can be adjusted by the thickness of the liquid crystal phase difference layer. Since the in-plane phase difference value is determined by the following formula (4), in order to obtain the desired in-plane phase difference value (Re(λ)), it is only necessary to adjust Δn(λ) and thickness d. The thickness of the liquid crystal phase difference layer is preferably 0.5μm to 5μm, more preferably 1μm to 3μm. The thickness of the liquid crystal phase difference layer can be measured using an interference film thickness meter, a laser microscope or a stylus film thickness meter. It should be noted that Δn(λ) depends on the molecular structure of the polymerizable liquid crystal compound described later.
[0307] Re(λ)=d×Δn(λ) (4)
[0308] (Where Re(λ) represents the in-plane phase difference at a wavelength of λnm, d represents the thickness, and Δn(λ) represents the birefringence at a wavelength of λnm.)
[0309] The positive C plate is not particularly limited as long as it has anisotropy in the thickness direction, but has the optical properties represented by formula (5) when there is no tilt or cholesteric orientation.
[0310] nx≈ny<nz (5)
[0311] The in-plane phase difference value Re(550) of the positive C plate at a wavelength of 550nm is usually in the range of 0 to 10nm, preferably in the range of 0 to 5nm. In addition, the phase difference value Rth(550) in the thickness direction at a wavelength of 550nm is usually in the range of -170nm to -10nm, preferably -150nm to -20nm, and more preferably -100nm to -40nm. If the phase difference value in the thickness direction is within this range, the anti-reflection properties from the oblique direction can be further improved.
[0312] (Method for producing liquid crystal phase difference layer)
[0313] The liquid crystal phase difference layer is usually formed by coating a composition for forming a liquid crystal phase difference layer on an orientation layer formed on a substrate layer, and polymerizing (curing) the polymerizable liquid crystal compound contained in the composition for forming the liquid crystal phase difference layer. The liquid crystal phase difference layer is usually a film formed by curing the polymerizable liquid crystal compound in an oriented state. If it is a cured film formed by polymerizing the polymerizable group of the polymerizable liquid crystal compound in a state of being oriented in a horizontal direction relative to the substrate surface, a phase difference can be generated in the observation plane. At this time, in the case where the polymerizable liquid crystal compound is a rod-shaped liquid crystal, it can be a positive A plate, and if the polymerizable liquid crystal compound is a disc-shaped liquid crystal, it can be a negative A plate.
[0314] (Polymerizable Liquid Crystal Compound in Liquid Crystal Retardation Layer Forming Composition)
[0315] The polymerizable liquid crystal compound contained in the composition for forming the liquid crystal phase difference layer refers to a liquid crystal compound having a polymerizable group, particularly a photopolymerizable group. As the polymerizable liquid crystal compound, a polymerizable liquid crystal compound known in the past can be used. The photopolymerizable group refers to a group that can participate in the polymerization reaction by reactive species, such as active free radicals, acids, etc., generated by a photopolymerization initiator. As a photopolymerizable group, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane, oxetane, etc. can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxirane and oxetane are preferred, and acryloyloxy is more preferred. Liquid crystal can be a thermotropic liquid crystal or a lyotropic liquid crystal. From the aspect of being able to perform dense film thickness control, a thermotropic liquid crystal is preferred. In addition, as a phase sequence structure in a thermotropic liquid crystal, it can be a nematic liquid crystal or a smectic liquid crystal. In addition, it can be a rod-shaped liquid crystal or a disc-shaped liquid crystal. The polymerizable liquid crystal compounds can be used alone or in combination of two or more.
[0316] As a polymerizable liquid crystal compound, from the viewpoint of exhibiting reverse wavelength dispersion, a liquid crystal having a mesomorphic structure in a T-type or H-type which further has birefringence in a direction perpendicular to the long axis direction of the molecule is preferred. From the viewpoint of obtaining a stronger dispersion, a T-type liquid crystal is more preferred. Specifically, for example, the structure of the T-type liquid crystal includes a compound represented by the following formula (I).
[0317] [Chemical formula 5]
[0318]
[0319] In formula (I), Ar represents a divalent aromatic group which may have a substituent. The divalent aromatic group preferably contains at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. When the number of aromatic groups contained in the divalent group Ar is 2 or more, the 2 or more aromatic groups may be bonded to each other by divalent bonding groups such as a single bond, -CO-O-, or -O-.
[0320] G 1 and G 2 Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by an oxygen atom, a sulfur atom or a nitrogen atom.
[0321] L 1 , L 2 , B1 and B 2 Each independently represents a single bond or a divalent linking group.
[0322] k and l each independently represent an integer from 0 to 3, and satisfy the relation 1 ≤ k + l. Here, when 2 ≤ k + l, B 1 and B 2 , G 1 and G 2 may be the same as or different from each other.
[0323] E 1 and E 2 Each independently represents an alkanediyl group having 1 to 17 carbon atoms (in Japanese: アルカンジイル基). Here, the hydrogen atoms contained in the alkanediyl group may be substituted by halogen atoms, and the -CH2- contained in the alkanediyl group may be replaced by -O-, -S-, -COO-. In the case of having multiple -O-, -S-, -COO-, they are not adjacent to each other. P 1 and P 2 Independently represent a polymerizable group or a hydrogen atom, and at least one is a polymerizable group.
[0324] G 1 and G 2 Each independently is preferably a 1,4-phenylenediyl group that can be substituted by at least one substituent selected from halogen atoms and alkyl groups having 1 to 4 carbon atoms, a 1,4-cyclohexanediyldiyl group that can be substituted by at least one substituent selected from halogen atoms and alkyl groups having 1 to 4 carbon atoms, more preferably a 1,4-phenylenediyl group substituted by a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyldiyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyldiyl group. In addition, it is preferred that at least one of the plurality of G 1 and G 2 is a divalent alicyclic hydrocarbon group. In addition, it is more preferably that at least one of the G 1 bonded to L 2 or L 1 and G 2 is a divalent alicyclic hydrocarbon group.
[0325] L 1 and L2 each independently are preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -, -R a3 COOR a4 -, -R a5 OCOR a6 -, R a7 OC=OOR a8-、-N=N-、-CR c =CR d -, or -C≡C-. Here, R a1 ~R a8 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms, and R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 Each independently is more preferably a single bond, -OR a2-1 -、-CH2-、-CH2CH2-、-COOR a4-1 -, or OCOR a6-1 -. Here, R a2-1 , R a4-1 , R a6-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and L 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or OCO-.
[0326] B 1 and B 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -、-R a11 COOR a12 -、-R a13 OCOR a14 -, or R a15 OC=OOR a16 -. Here, R a9 ~R a16 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH2-、-CH2CH2-、-COOR a12 -1 -, or OCOR a14-1 -. Here, R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and B 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or OCOCH2CH2-.
[0327] From the viewpoint of exhibiting reverse wavelength dispersion, k and l are preferably in the range of 2≤k+l≤6, preferably k+1=4, and more preferably k=2 and 1=2. If k=2 and 1=2, a symmetrical structure is obtained, which is preferred.
[0328] E 1 and E 2 Each independently is preferably an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms.
[0329] As P 1 or P 2 The polymerizable group shown in the figure includes epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxiranyl and oxetanyl, etc. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxiranyl and oxetanyl are preferred, and acryloyloxy is more preferred.
[0330] Ar preferably has at least one selected from an aromatic hydrocarbon ring that may have a substituent, an aromatic heterocycle that may have a substituent, and an electron-withdrawing group. As the aromatic hydrocarbon ring, for example, benzene ring, naphthalene ring, anthracene ring, etc. can be cited, preferably benzene ring, naphthalene ring. As the aromatic heterocycle, furan ring, benzofuran ring, pyrrole ring, indole ring, thiophene ring, benzothiophene ring, pyridine ring, pyrazine ring, pyrimidine ring, triazole ring, triazine ring, pyrroline ring, imidazole ring, pyrazole ring, thiazole ring, benzothiazole ring, thienothiazole ring, oxazole ring, benzoxazole ring and phenanthroline ring etc. can be cited. Among them, preferably have thiazole ring, benzothiazole ring or benzofuran ring, further preferably have benzothiazolyl. In addition, when Ar includes nitrogen atom, the nitrogen atom preferably has π electrons.
[0331] In formula (I), the total number Nπ of π electrons contained in the divalent aromatic group represented by Ar is preferably 8 or more, more preferably 10 or more, further preferably 14 or more, and particularly preferably 16 or more. It is preferably 30 or less, more preferably 26 or less, and further preferably 24 or less.
[0332] As the aromatic group represented by Ar, for example, the following groups can be preferably mentioned.
[0333] [Chemical formula 6]
[0334]
[0335] In the formulas (Ar-1) to (Ar-23), the * symbol represents a connecting portion, and Z 0 , Z 1 and Z 2Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.
[0336] Q 1 , Q 2 and Q 3 Each independently represents -CR 2’ R 3’ -、-S-、-NH-、-NR 2’ -, -CO- or O-, R 2’ and R 3’ Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0337] J 1 and J 2 Each independently represents a carbon atom or a nitrogen atom.
[0338] Y 1 , Y 2 and Y 3 Each independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group which may be substituted.
[0339] W 1 and W 2 Each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom, and m represents an integer of 0-6.
[0340] As Y 1 , Y 2 and Y 3 The aromatic hydrocarbon group in the group includes aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as phenyl, naphthyl, anthracenyl, phenanthrenyl, and biphenyl, preferably phenyl and naphthyl, and more preferably phenyl. The aromatic heterocyclic group includes aromatic heterocyclic groups having 4 to 20 carbon atoms, such as furanyl, pyrrolyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl, which contain at least one hetero atom such as a nitrogen atom, an oxygen atom, or a sulfur atom, preferably furanyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl.
[0341] Y 1 , Y 2 and Y 3Each independently may be a polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group which may be substituted. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from a collection of aromatic rings. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from a collection of aromatic rings.
[0342] Z 0 , Z 1 and Z 2 Each of Z is independently preferably a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 More preferably, a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2 More preferred are a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group and a cyano group.
[0343] Q 1 , Q 2 and Q 3 Preferred are -NH-, -S-, -NR 2’ -、-O-,R 2’ A hydrogen atom is preferred, and -S-, -O-, and -NH- are particularly preferred.
[0344] Among formulae (Ar-1) to (Ar-23), formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.
[0345] In the formulas (Ar-16) to (Ar-23), Y 1 The nitrogen atom and Z 0 Together, they form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include the aromatic heterocyclic groups described above as aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. The aromatic heterocyclic group may have a substituent. In addition, Y 1 The nitrogen atom and Z 0 Together, they are the above-mentioned optionally substituted polycyclic aromatic hydrocarbon groups or polycyclic aromatic heterocyclic groups, for example, benzofuran ring, benzothiazole ring, benzoxazole ring, etc.
[0346] Among the polymerizable liquid crystal compounds, compounds with a maximum absorption wavelength of 300 to 400 nm are preferred. When a photopolymerization initiator is included in the polymerizable liquid crystal composition, it is possible to carry out polymerization reaction and gelation of the polymerizable liquid crystal compound during long-term storage. However, if the maximum absorption wavelength of the polymerizable liquid crystal compound is 300 to 400 nm, even if it is exposed to ultraviolet light during storage, the generation of reactive species from the photopolymerization initiator and the polymerization reaction and gelation of the polymerizable liquid crystal compound caused by the reactive species can be effectively suppressed. Therefore, it becomes advantageous in terms of the long-term stability of the polymerizable liquid crystal composition, and the uniformity of the orientation and film thickness of the obtained phase difference layer can be improved. It should be noted that the maximum absorption wavelength of the polymerizable liquid crystal compound can be measured in a solvent using an ultraviolet-visible spectrophotometer. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, and chloroform and the like can be cited as examples.
[0347] Examples of the disc-shaped polymerizable liquid crystal compound include a compound containing a group represented by formula (W) (hereinafter, also referred to as a “polymerizable liquid crystal compound (W)”).
[0348] [Chemical formula 7]
[0349]
[0350] [In formula (W), R 40 It represents the following formulas (W-1) to (W-5).]
[0351] [Chemical formula 8]
[0352]
[0353] [In formulas (W-1) to (W-5),
[0354] X 40 and Z 40 Each independently represents an alkanediyl group having 1 to 12 carbon atoms, wherein the hydrogen atoms contained in the alkanediyl group may be substituted by an alkoxy group having 1 to 5 carbon atoms, wherein the hydrogen atoms contained in the alkoxy group may be substituted by a halogen atom. In addition, -CH2- constituting the alkanediyl group may be substituted by -O- or -CO-.
[0355] m2 represents an integer.]
[0356] Examples of the rod-shaped polymerizable liquid crystal compound include compounds represented by formula (II), formula (III), formula (IV), formula (V), formula (VI), or formula (VII).
[0357] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12 (II)
[0358] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11 (III)
[0359] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12 (IV)
[0360] P11-B11-E11-B12-A11-B13-A12-B14-A13-F11 (V)
[0361] P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12 (VI)
[0362] P11-B11-E11-B12-A11-B13-A12-F11 (VII)
[0363] [In formulas (II) to (VII),
[0364] A11 to A14 each independently represent a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group. The hydrogen atoms contained in the divalent alicyclic hydrocarbon group and the divalent aromatic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cyano group or a nitro group, and the hydrogen atoms contained in the alkyl group having 1 to 6 carbon atoms and the alkoxy group having 1 to 6 carbon atoms may be substituted with a fluorine atom.
[0365] B11 and B17 each independently represent -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -CO-NR 16 -、-NR 16 -CO-, -CO-, -CS-, or a single bond. 16 It represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0366] B12 to B16 each independently represent -C≡C-, -CH=CH-, -CH2-CH2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -、-NR 16-C(=O)-, -OCH2-, -OCF2-, -CH2O-, -CF2O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH- or a single bond.
[0367] E11 and E12 each independently represent an alkanediyl group having 1 to 12 carbon atoms, wherein the hydrogen atoms contained in the alkanediyl group may be substituted by an alkoxy group having 1 to 5 carbon atoms, wherein the hydrogen atoms contained in the alkoxy group may be substituted by a halogen atom, and wherein -CH2- constituting the alkanediyl group may be substituted by -O- or -CO-.
[0368] F11 represents a hydrogen atom, an alkyl group having 1 to 13 carbon atoms, an alkoxy group having 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxyl group, a hydroxymethyl group, a formyl group, a sulfo group (-SO3H), a carboxyl group, an alkoxycarbonyl group having 1 to 10 carbon atoms, or a halogen atom, and the -CH2- constituting the alkyl group and the alkoxy group may be replaced by -O-.
[0369] P11 and P12 each independently represent a polymerizable group.]
[0370] Relative to 100 parts by mass of the solid content of the composition for forming a liquid crystal phase difference layer, the content of the polymerizable liquid crystal compound in the composition for forming a liquid crystal phase difference layer is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 95 parts by mass. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the perspective of the orientation of the obtained liquid crystal phase difference layer. It should be noted that in this specification, the solid content of the polymerizable liquid crystal composition refers to all components after removing volatile components such as organic solvents from the polymerizable liquid crystal composition.
[0371] (Other components of the composition for forming a liquid crystal retardation layer)
[0372] The composition for forming a liquid crystal retardation layer may contain reactive additives such as a solvent, a leveling agent, a polymerization initiator, a photosensitizer, a polymerization inhibitor, a crosslinking agent, and an adhesion agent in addition to the polymerizable liquid crystal compound. From the viewpoint of processability, it preferably contains a solvent and a leveling agent.
[0373] (Solvent for Liquid Crystal Retardation Layer Forming Composition)
[0374] Generally, the viscosity of the polymerizable liquid crystal compound is high, so by dissolving the polymerizable liquid crystal compound in a solvent, coating becomes easy, and as a result, a liquid crystal phase difference layer is easily formed in many cases. As a solvent, a solvent that can completely dissolve the polymerizable liquid crystal compound is preferred, and a solvent that is inactive to the polymerization reaction of the polymerizable liquid crystal compound is preferred.
[0375] As the solvent, there can be mentioned alcohol solvents such as methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone or propylene glycol methyl ether acetate and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane and heptane; aromatic hydrocarbon solvents such as toluene and xylene, nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated solvents such as chloroform and chlorobenzene; amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, etc. These solvents can be used alone or in combination of two or more.
[0376] The content of the solvent is preferably 50 to 98% by mass relative to the total amount of the phase difference layer forming composition. In other words, the content of the solid component in the phase difference layer film forming composition is preferably 2 to 50% by mass, and more preferably 5 to 30% by mass. If the content of the solid component is less than 50% by mass, the viscosity of the phase difference layer forming composition becomes low, so the thickness of the phase difference layer becomes roughly uniform, and thus there is a tendency that the phase difference layer is not easy to produce unevenness. In addition, the content of the solid component can be determined by considering the thickness of the phase difference layer to be manufactured.
[0377] (Leveling agent for liquid crystal retardation layer forming composition)
[0378] The composition for forming a phase difference layer may contain a leveling agent. The leveling agent refers to an additive that has the function of adjusting the fluidity of the composition and making the film obtained by coating the composition flatter, and examples thereof include organic modified silicone-based, polyacrylate-based, and perfluoroalkyl-based leveling agents. Among them, in the case of horizontal orientation, polyacrylate-based leveling agents and perfluoroalkyl-based leveling agents are preferred, and in the case of vertical orientation, organic modified silicone-based leveling agents and perfluoroalkyl-based leveling agents are preferred.
[0379] When the composition for forming a phase difference layer contains a leveling agent, its content is preferably 0.01 to 5 parts by mass, and more preferably 0.05 to 3 parts by mass relative to 100 parts by mass of the content of the polymerizable liquid crystal compound. If the content of the leveling agent is within the above range, there is a tendency to easily orient the polymerizable liquid crystal compound horizontally and to make the resulting phase difference layer smoother. If the content of the leveling agent exceeds the above range relative to the content of the polymerizable liquid crystal compound, there is a tendency for the resulting phase difference layer to be prone to unevenness. It should be noted that the composition for forming a phase difference layer may contain two or more leveling agents.
[0380] (Polymerization initiator for liquid crystal retardation layer forming composition)
[0381] The phase difference layer forming composition may contain a polymerization initiator. A polymerization initiator is a compound that can initiate a polymerization reaction of a polymerizable liquid crystal compound or the like. As the polymerization initiator, a photopolymerization initiator that generates active free radicals by the action of light is preferred from the viewpoint of being independent of the phase state of the thermotropic liquid crystal.
[0382] As long as the photopolymerization initiator is a compound capable of initiating a polymerization reaction of a polymerizable liquid crystal compound, a known photopolymerization initiator can be used. Specifically, a photopolymerization initiator capable of generating active free radicals or acids by the action of light can be cited, among which a photopolymerization initiator generating free radicals by the action of light is preferred. The photopolymerization initiator can be used alone or in combination of two or more.
[0383] As the photopolymerization initiator, a known photopolymerization initiator can be used. For example, as a photopolymerization initiator that generates active free radicals, self-cleaving benzoin compounds, acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, oxime ester compounds, acylphosphine oxide compounds, azo compounds, etc. can be used. Hydrogen-abstracting benzophenone compounds, alkylphenone compounds, benzoin ether compounds, benzyl ketal compounds, dibenzosuberone compounds, anthraquinone compounds, xanthone compounds, thioxanthone compounds, halogenated acetophenone compounds, dialkoxyacetophenone compounds, halogenated bisimidazole compounds, halogenated triazine compounds, triazine compounds, etc. can be used. As a photopolymerization initiator that generates an acid, iodonium salts and sulfonium salts can be used. From the viewpoint of excellent reaction efficiency at low temperature, self-cleavage type photopolymerization initiators are preferred, and acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, and oxime ester compounds are particularly preferred.
[0384] The content of the polymerization initiator in the phase difference layer forming composition can be appropriately adjusted according to the type and amount of the polymerizable liquid crystal compound, and is generally 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound. If the content of the polymerization initiator is within the above range, polymerization can be performed without disturbing the orientation of the polymerizable liquid crystal compound.
[0385] (Sensitizer for Liquid Crystal Retardation Layer Forming Composition)
[0386] The phase difference layer forming composition may contain a sensitizer. As the sensitizer, a photosensitizer is preferred. Examples of the sensitizer include: xanthone compounds such as xanthone and thioxanthone (e.g., 2,4-diethylthioxanthone, 2-isopropylthioxanthone, etc.); anthracene compounds such as anthracene and anthracene containing an alkoxy group (e.g., dibutoxyanthracene, etc.); phenothiazine and rubrene, etc.
[0387] When the phase difference layer forming composition contains a sensitizer, the polymerization reaction of the polymerizable liquid crystal compound contained in the phase difference layer forming composition can be further promoted. The amount of the sensitizer used is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound.
[0388] (Antioxidant for Liquid Crystal Retardation Layer-Forming Composition)
[0389] The phase difference layer forming composition may contain an antioxidant from the viewpoint of stably advancing the polymerization reaction. The antioxidant can control the degree of progress of the polymerization reaction of the polymerizable liquid crystal compound.
[0390] The antioxidant may be, for example, a primary antioxidant selected from phenolic antioxidants, amine antioxidants, quinone antioxidants, and nitroso antioxidants, or a secondary antioxidant selected from phosphorus antioxidants and sulfur antioxidants.
[0391] When the phase difference layer forming composition contains an antioxidant, the content of the antioxidant is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and further preferably 0.5 to 8 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound. The antioxidant may be used alone or in combination of two or more. If the content of the antioxidant is within the above range, polymerization can be performed without disturbing the orientation of the polymerizable liquid crystal compound.
[0392] (Reactive Additives in Liquid Crystal Retardation Layer-Forming Composition)
[0393] The phase difference layer forming composition may contain a reactive additive. As a reactive additive, it is preferred to have a carbon-carbon unsaturated bond, an active hydrogen reactive group, or a mercapto group in its molecule. It should be noted that the "active hydrogen reactive group" referred to herein refers to a group reactive to a group having active hydrogen such as a carboxyl group (-COOH), a hydroxyl group (-OH), and an amino group (-NH2), and representative examples thereof include a glycidyl group, an oxazoline group, a carbodiimide group, an aziridine group, an imide group, an isocyanate group, a thioisocyanate group, and a maleic anhydride group. The number of reactive groups possessed by the reactive additive is usually 1 to 20, preferably 1 to 10, respectively.
[0394] (Alignment layer 54 used in the manufacture of liquid crystal phase difference layer)
[0395] The alignment layer has an alignment regulating force for aligning the polymerizable liquid crystal compound in a desired direction.
[0396] The orientation layer makes it easy to orient the liquid crystal of the polymerizable liquid crystal compound. The state of liquid crystal orientation such as horizontal orientation, vertical orientation, mixed orientation, and tilted orientation varies according to the properties of the orientation layer and the polymerizable liquid crystal compound, and their combination can be selected arbitrarily. For example, if the orientation layer is a material that exhibits horizontal orientation as an orientation limiting force, the polymerizable liquid crystal compound can form a horizontal orientation or a mixed orientation, and if it is a material that exhibits vertical orientation, the polymerizable liquid crystal compound can form a vertical orientation or a tilted orientation. Expressions such as horizontal and vertical indicate the direction of the optical axis of the oriented polymerizable liquid crystal compound when the plane of the phase difference layer is used as a reference. For example, vertical orientation refers to having an optical axis of the oriented polymerizable liquid crystal compound in a direction perpendicular to the plane of the phase difference layer. The vertical mentioned here refers to 90°±20° relative to the plane of the phase difference layer.
[0397] Regarding the orientation restraining force, when the orientation layer is formed of an orientation polymer, it can be arbitrarily adjusted according to the surface state and friction conditions, and when it is formed of a photo-orientation polymer, it can be arbitrarily adjusted according to polarized light irradiation conditions, etc. In addition, the liquid crystal orientation can also be controlled by selecting the surface tension, liquid crystal properties, etc. of the polymerizable liquid crystal compound.
[0398] As an orientation layer formed between the substrate layer and the liquid crystal phase difference layer, it is preferably an orientation layer that is insoluble in the solvent used when forming the phase difference layer on the orientation layer and has heat resistance in the heat treatment for removing the solvent and orienting the liquid crystal. As the orientation layer, an orientation layer comprising an oriented polymer, a photo-orientation layer and a groove orientation layer, a stretched film stretched along the orientation direction, etc. can be cited. In the case of being applied to a long roll film, from the viewpoint of being able to easily control the orientation direction, a photo-orientation layer is preferred.
[0399] The thickness of the alignment layer is usually in the range of 10 nm to 5000 nm, preferably in the range of 10 nm to 1000 nm, and more preferably in the range of 30 to 300 nm.
[0400] As the oriented polymer used in the rubbing oriented layer, polyamides, gelatins, polyimides with amide bonds in the molecule and polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylates, etc., which are hydrolyzates thereof, can be cited. Among them, polyvinyl alcohol is preferred. These oriented polymers can be used alone or in combination of two or more.
[0401] As a method of rubbing, there is mentioned a method of bringing a film of an oriented polymer formed on the surface of a substrate layer by applying an oriented polymer composition to a substrate and annealing the film into contact with a rubbing roller wound with a rubbing cloth and rotating.
[0402] The photo-alignment layer comprises a polymer, oligomer or monomer having a photoreactive group. The photo-alignment layer obtains an alignment restraining force by irradiating polarized light. From the viewpoint that the direction of the alignment restraining force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light, a photo-alignment layer is more preferred.
[0403] A photoreactive group refers to a group that generates liquid crystal orientation capability by irradiation with light. Specifically, it is a group that generates a photoreaction that is the origin of the liquid crystal orientation capability, such as an orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction of a molecule generated by irradiation with light. In the photoreactive group, from the aspect of excellent orientation, a group that generates a dimerization reaction or a photocrosslinking reaction is preferred. As a photoreactive group capable of the above-mentioned reaction, a photoreactive group having an unsaturated bond, particularly a double bond, is preferably a group having at least one selected from a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond).
[0404] As photoreactive groups having C=C bonds, for example, vinyl, polyene, stilbene, stilbazolyl, stilbazolyl, chalcone and cinnamoyl groups can be cited. From the viewpoint of easy control of reactivity and the viewpoint of orientation restriction during photo-orientation, chalcone and cinnamoyl groups are preferred. As photoreactive groups having C=N bonds, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having N=N bonds, groups with azobenzene as the basic structure, such as azonaphthyl, aromatic heterocyclic azo, disazo and formazan, can be cited. As photoreactive groups having C=O bonds, benzophenone, coumarin, anthraquinone and maleimide groups can be cited. These groups may have a substituent such as an alkyl group, an alkoxy group, an aryl group, an allyloxy group, a cyano group, an alkoxycarbonyl group, a hydroxyl group, a sulfonic acid group, and a halogenated alkyl group.
[0405] When irradiating polarized light, it can be a form of directly irradiating polarized light from the film surface, or it can be a form of irradiating polarized light from the substrate layer side and transmitting the polarized light. In addition, the polarized light is particularly preferably substantially parallel light. Regarding the wavelength of the polarized light irradiated, it is better to have a photoreactive group of a polymer or monomer with a photoreactive group. The wavelength of polarized light in the wavelength region where the photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) in the range of 250 to 400nm is particularly preferred. As the light source used in the polarized light irradiation, xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF can be cited, and high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are more preferred. These lamps are preferred because the luminous intensity of ultraviolet light with a wavelength of 313nm is large. The light from the above-mentioned light source is irradiated through an appropriate polarizer, thereby irradiating polarized light. As the polarizer, polarizing prisms such as polarizing filters, Glan-Thomson prisms, and Glan-Taylor prisms, and wire grid polarizers can be used.
[0406] (Base material layer 80)
[0407] As the above-mentioned substrate layer 80 for forming the liquid crystal phase difference layer, a glass substrate and a film substrate can be cited, and a film substrate is preferred. From the perspective of being able to be manufactured continuously, a long roll film is more preferred. As the resin constituting the film substrate, for example, chain polyolefins such as polyethylene and polypropylene; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as triacetyl cellulose, diacetyl cellulose and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide and polyphenylene ether, etc. Among them, from the perspective of transparency when used in optical film applications, a film substrate selected from any one of triacetyl cellulose, cyclic olefin resins, polymethacrylate, and polyethylene terephthalate is more preferred.
[0408] Examples of commercially available cellulose ester substrates include "FUJITAC Film" (manufactured by Fuji Photo Film Co., Ltd.); "KC8UX2M", "KC8UY" and "KC4UY" (manufactured by Konica Minolta Opto Co., Ltd.). Examples of commercially available cyclic olefin resins include "Topas" (registered trademark) (manufactured by Ticona (Germany)), "ARTON" (registered trademark) (manufactured by JSR Corporation), "ZEONOR" (registered trademark), "ZEONEX" (registered trademark) (manufactured by ZEON Co., Ltd. of Japan) and "APEL" (registered trademark) (manufactured by Mitsui Chemicals, Inc.). Such cyclic olefin resins can be made into films by known methods such as solvent casting and melt extrusion to form substrates. Commercially available cyclic olefin resin substrates can also be used. Examples of commercially available cyclic olefin resin substrates include “Esushina” (registered trademark), “SCA40” (registered trademark) (all manufactured by Sekisui Chemical Co., Ltd.), “ZeonorFilm” (registered trademark) (manufactured by Optes Co., Ltd.), and “Arton Film” (registered trademark) (manufactured by JSR Corporation).
[0409] The thickness of the substrate layer 80 is preferably thin enough to be handled in a practical manner, but if it is too thin, there is a tendency for the strength to decrease and the processability to be poor. The thickness of the substrate layer 80 is usually 5 μm to 300 μm, preferably 10 μm to 200 μm, and more preferably 10 to 50 μm. In addition, by peeling off the substrate layer and transferring the phase difference layer, a further thin film effect can be obtained. The substrate layer 80 may be a laminate.
[0410] The overall rigidity (the sum of Young's modulus×thickness) of the base material layer is not particularly limited, and may be more than 250,000 N / m or may be 250,000 N / m or less.
[0411] In manufacturing Figure 4 In the case of a phase element 50 such as (b), a laminated film having a structure of a first liquid crystal phase difference layer 52 / orientation layer 54 / substrate layer 80 and a laminated film having a structure of a second liquid crystal phase difference layer 58 / orientation layer 54 / substrate layer 80 are prepared, and the two laminated films are bonded together with a phase element adhesive in a manner that the first liquid crystal phase difference layer 52 and the second liquid crystal phase difference layer 58 are opposite to each other, and the phase element adhesive is cured by UV irradiation or the like, and then the substrate layer and the orientation layer of one of them are peeled off.
[0412] The phase element adhesive is not particularly limited, and the phase element adhesives exemplified in the polarizing plate adhesive layer, the phase element adhesives described in the active energy ray-curable adhesive layer 40 , and the like can be used as appropriate.
[0413] (Method for Manufacturing Optical Layered Body 100)
[0414] Figure 1 Such an optical laminate 100 can be manufactured, for example, by laminating the laminated film of the substrate layer 80 / phase element 50 to the polarizing laminate 30 using an active energy ray-curable adhesive. Usually, such an optical laminate 100 is manufactured in the form of a long sheet (e.g., a roll). The coating method of the active energy ray-curable adhesive, the pretreatment of any coating surface, etc. can appropriately utilize the contents exemplified in the polarizing plate adhesive layer.
[0415] Step (2) Active Energy Ray Irradiation Step
[0416] Next, the optical layered body 100 is irradiated with active energy rays to cure the layer 40 of the active energy ray-curable adhesive.
[0417] The irradiation direction of the active energy ray is not limited, and the irradiation may be from the polarizing laminate side, from the substrate layer 80 side, or from both sides. In the case where the polarizing laminate 30 has a protective film 37, etc., it is appropriate to irradiate the active energy ray at least from the substrate layer 80 side. As long as the conditions are such that curing can be achieved, the irradiation conditions are not particularly limited, and the light irradiation intensity is preferably 10 mW / cm 2 Above 1,000mW / cm 2 It should be noted that the irradiation intensity is preferably an intensity in the wavelength region effective for the activation of the photocationic polymerization initiator or the photoradical polymerization initiator. The irradiation is performed once or multiple times with such a light irradiation intensity, and the accumulated light amount is preferably set to 10 mJ / cm 2 More preferably, 100 mJ / cm 2 Above and 1,000mJ / cm 2 the following.
[0418] The light source used for polymerizing and curing the active energy ray-curable adhesive layer is not particularly limited, and examples thereof include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.
[0419] Step (3) Roller conveying step
[0420] In step (3), after the irradiation in step (2), the optical laminate 100 is transported while being brought into contact with the surface of at least one transport roller. The transported film is wound around a core material or the like to obtain a raw material roll of a circular polarizing plate. Furthermore, in the transporting step (3), at least one transport roller is in contact with the polarizing laminate 30 of the optical laminate 100, and the wrap angle θ of the transport roller in contact with the polarizing laminate 30 of the optical laminate 100 is 150° or less.
[0421] The wrap angle θ may be 100° or less, 80° or less, or 70° or less. In step (3), when there are multiple conveying rollers in contact with the polarizing laminate 30 of the optical laminate 100, the wrap angle of all conveying rollers is set to be less than the upper limit, for example, 150° or less.
[0422] Specifically, for example, you can use Figure 5 The combination of the conveying rollers R1 and R2 is used for conveying. Figure 5 In the embodiment, the upper side of the optical stack 100 is the polarizing stack 30, and the lower side of the optical stack 100 is the substrate layer 80. In this example, the substrate layer 80 of the optical stack 100 is transported while being in contact with the surface of the transport roller R1, and the polarizing stack 30 of the optical stack 100 is transported while being in contact with the surface of the transport roller R2.
[0423] The wrap angle θ of the transport roller R2 refers to the angle θ formed by a line connecting the axis P of the transport roller and the point T1 where the outer peripheral surface of the transport roller starts to contact the optical layer 100, and a line connecting the axis P of the transport roller and the point T2 where the outer peripheral surface of the transport roller ends contact with the optical layer 100 in a cross section perpendicular to the axis P of the transport roller R2.
[0424] When the sum of the Young's modulus x thickness (rigidity) of the substrate layer 80 is 250,000 N / m or less, in the conveying step (3), the wrap angle α between the substrate layer 80 of the optical laminate 100 and the contacting conveying roller is set to 150° or less. The wrap angle α may be 100° or less, 80° or less, or 70° or less. For example, Figure 5 In the example, the wrap angle α of the transport roller R1 is set to, for example, 150° or less. When there are a plurality of transport rollers in contact with the base layer 80 of the optical layered body 100 , the wrap angle α of all the transport rollers is set to be smaller than the above upper limit.
[0425] (Circular polarizing plate raw material roll)
[0426] The circular polarizing plate 100' thus obtained can be a raw material roll having Figure 6 The layer structure is as shown.
[0427] That is, Figure 6 As shown, the original material roll of the circular polarizing plate 100 ′ includes the polarizing laminate 30 , a layer 40 ′ of a cured product of an active energy ray-curable adhesive, a phase element 50 , and a base material layer 80 in this order.
[0428] The polarizing laminate 30 of the circular polarizing plate 100 ′ may not include the protective film or the separator 37 , and the circular polarizing plate 100 ′ may not include the base material layer 80 .
[0429] The surface of the layer 40' of the cured product of the active energy ray-curable adhesive of the raw material roll of the circular polarizing plate 100' on the side opposite to the polarizing laminate 30 does not have a concave portion with a maximum depth exceeding 500nm periodically formed along the length direction (MD direction) of the raw material roll of the circular polarizing plate. The concave portion in this specification refers to a concave portion periodically formed in the length direction of the raw material roll of the circular polarizing plate. The period is determined by the outer diameter of the conveying roller and can usually be 10 to 100 cm.
[0430] Specifically, the maximum depth of the concave portion refers to the concave portion and the surface unevenness in the vicinity thereof visually observed on the surface of the layer 40' of the cured product of the active energy ray-curable adhesive opposite to the polarizing laminate 30 in the circular polarizing plate 100' measured by the optical interference method, and a cross-sectional curve in the width direction (TD direction) passing through the deepest part of the concave portion is obtained based on the obtained surface shape data, such as Figure 7 As shown, the height Z1 of the lowest part of the concave portion A1 is equal to the higher of the heights Z2 and Z3 of the highest parts of the two convex portions A2 and A3 on both sides of the concave portion A1 (in Figure 7 In the example of Z3), the difference ZT is obtained. The length of the X axis in the cross-sectional curve (reference length) can be set to about 1000 to 10000 μm.
[0431] In one embodiment, even if the total of Young's modulus × thickness (rigidity) of the substrate layer 80 is less than 250,000 N / m, the surface of the layer 40' of the cured product of the active energy ray-curing adhesive of the raw material roll of the circular polarizing plate 100' on the side opposite to the phase element 50 does not have recesses with a maximum depth exceeding 500 nm periodically formed in the length direction (MD direction) of the raw material roll of the circular polarizing plate.
[0432] The width of the circularly polarizing plate of the original material roll is not particularly limited, and may be 500 mm or more, or 1000 mm or more.
[0433] The length of the circularly polarizing plate of the original material roll is not particularly limited, and may be twice or more longer than the normal width to be 100 m or more, or may be 500 m or more.
[0434] (Effect)
[0435] In the present embodiment, the above-mentioned shear stress α of the layer 40' of the cured product of the active energy ray-curable adhesive in the optical laminate 100 is less than 100 Pa. This means that the cured product layer 40' is softer than usual. It is clear that in the roller conveyance of such an optical laminate 100, when the total of the Young's modulus × thickness (rigidity) of the protective film of the polarizing laminate 30 is less than 250,000 N / m, in other words, when the rigidity of the polarizing laminate 30 is small, if the wrap angle of the conveying roller in contact with the polarizing laminate 30 is too large, the surface of the layer 40' of the cured product of the active energy ray-curable adhesive on the side of the polarizing laminate is sunken due to foreign matter on the surface of the conveying roller, etc., resulting in a defect of a concave portion with a maximum depth exceeding 500 nm.
[0436] In this embodiment, the depth of periodic recesses (punches) generated on the surface of the polarizing laminate 30 in the layer 40' of the cured product of the active energy ray-curable adhesive due to foreign matter on the surface of the conveying roller and the like can be reduced by reducing the wrap angle θ of the conveying roller in contact with the polarizing laminate 30. If the wrap angle of the conveying roller is reduced, the conveying line becomes longer, so those skilled in the art generally do not reduce the wrap angle.
[0437] In addition, when the total of the Young's modulus × thickness (rigidity) of the substrate layer 80 is less than 250,000 N / m, by setting the wrap angle α of the conveying roller in contact with the substrate layer 80 to less than a specified angle, the periodic recesses generated on the surface of the phase element side in the layer of the cured product of the active energy ray-curing adhesive can be further reduced.
[0438] The obtained raw material roll of the circular polarizing plate does not have a concave portion with a maximum depth exceeding 500nm formed periodically along the length direction of the circular polarizing plate on the surface of the layer 40' of the cured product of the active energy ray-curable adhesive opposite to the polarizing laminate 30. The circular polarizing plate having a concave portion with a maximum depth exceeding 500nm is easily dented, resulting in a poor appearance and becoming a defective product. According to the raw material roll of this embodiment, the surface on the side of the polarizing laminate does not have a periodic concave portion with a maximum depth exceeding 500nm, thereby achieving an effect of improving the yield when a single piece of the polarizing plate is obtained.
[0439] In addition, even if the rigidity value of the substrate layer 80 of the obtained circular polarizing plate raw material roll is less than 250,000 N / m, the surface of the layer 40' of the cured product of the active energy ray-curing adhesive on the side opposite to the phase element 50 does not have recesses with a maximum depth exceeding 500 nm periodically formed in the length direction of the circular polarizing plate.
[0440] Example
[0441] <Measurement of Shear Stress α>
[0442] The shear stress α was measured using a viscoelasticity measuring device (MCR-301, Anton Paar). As described above, the shear stress α refers to the maximum stress when a cured adhesive in the shape of a disk with a diameter of 8 mm and a thickness of 5 μm is clamped by a pair of parallel plates and vibrated around the central axis of the disk at a rotation angle of 1 mrad and a frequency of 1 Hz to impart a torsional moment.
[0443] Specifically, the environment was set at a temperature of 25° C. and a humidity of 50%. The adhesive area was set to a diameter of 8 mm and the adhesive thickness was set to 5 μm. UV light irradiation was performed for 30 seconds to obtain a cured sample.
[0444] As UV irradiation, 30mW / cm 2 Irradiate with UVA from a xenon halogen lamp for 30 seconds.
[0445] <Defect Inspection Method for Circularly Polarizing Plate Raw Material Roll>
[0446] A method for inspecting the defects of the concave portion generated on the surface of the side opposite to the polarizing laminate 30 in the layer 40' of the cured product of the active energy ray-curable adhesive possessed by the raw material roll of the circular polarizing plate is described. First, for each 1.5 m at the beginning and end of the winding of the raw material roll of the circular polarizing plate, the light of the three-wavelength tube fluorescent lamp is irradiated on the surface of the circular polarizing plate, and the presence of the concave portion defect is visually inspected. If the concave portion defect is a concave portion defect with a maximum depth exceeding 500nm, it looks like a darker shadow compared to the surrounding area, so the presence or absence of the concave portion defect can be confirmed by visual inspection.
[0447] In addition, for the concave defects found by visual inspection, the maximum depth of the concave was measured. The surface shape measuring device and the measuring conditions are as follows.
[0448] Measuring device: VertScan (registered trademark) (Ryoka Systems Co., Ltd., model R5500G)
[0449] Objective lens (magnification): 2.5 times
[0450] Measuring range: 3700×2800μm
[0451] Resolution: 640 × 480 pixels
[0452] Measurement mode: Wave mode
[0453] Surface correction: 4 times processing
[0454] Specifically, in the circular polarizing plate 100', the concave portion and the surface unevenness near it that are visually observed on the surface of the side opposite to the polarizing laminate 30 in the layer 40' of the cured product of the active energy ray-curing adhesive are measured by the optical interference method. A cross-sectional curve in the width direction (TD direction) through the deepest part of the concave portion is obtained based on the obtained surface shape data, and the difference between the height Z1 of the lowest part of the concave portion and the height of the highest part of each of the two convex portions on both sides of the concave portion is obtained. The length (reference length) of the X-axis in the cross-sectional curve is set to 3700μm. According to the optical interference method, the depth of each concave portion of the surface on the side of the polarizing laminate 30 in the layer 40 of the active energy ray-curing adhesive and the surface on the side of the phase element 50 in the layer 40 of the active energy ray-curing adhesive can be measured.
[0455] It should be noted that the recesses formed periodically along the length direction of the circular polarizing plate on the surface of the side opposite to the polarizing laminate or the side opposite to the phase element in the layer of the cured product of the active energy ray-curable adhesive are generated due to foreign matter on the surface of the conveying roller. Therefore, once the recesses are generated during the conveying using the conveying roller, the same recesses continue to be generated periodically at intervals corresponding to the length of the outer circumference of the roller. Therefore, if no periodic recesses are visually confirmed at 1.5m at the beginning of the winding of the original material roll of the circular polarizing plate and 1.5m at the end of the winding, it can be inferred that there are no periodic recesses with a maximum depth exceeding 500nm in the entire original material roll.
[0456] <Preparation of components of circularly polarizing plate raw material roll>
[0457] (Production of Linear Polarizer)
[0458] A polyvinyl alcohol film having a thickness of 20 μm, a degree of polymerization of 2400, and a saponification degree of 99% or more was uniaxially stretched on a hot roller to a stretching ratio of 4.1 times, and while maintaining the tension, was immersed in a dyeing bath containing 0.05 parts by mass of iodine and 5 parts by mass of potassium iodide relative to 100 parts by mass of water at 28° C. for 60 seconds.
[0459] Next, the film was immersed in a boric acid aqueous solution 1 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide relative to 100 parts by mass of water at 64°C for 110 seconds. Next, the film was immersed in a boric acid aqueous solution 2 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide relative to 100 parts by mass of water at 67°C for 30 seconds. Then, the film was washed with pure water at 10°C and dried to obtain a linear polarizer 1. The thickness of the polarizer 1 was 8 μm, and the boron content was 4.3% by mass.
[0460] (Preparation of protective films A, B, C, peelable film D, base film E, and pellicle F)
[0461] Prepare the following membranes.
[0462] Protective film A: Cycloolefin polymer (COP) film (thickness: 13 μm) with a rigidity of 29770 N / m.
[0463] Protective film B: Cycloolefin polymer (COP) film (thickness: 26 μm) with a rigidity of 59540 N / m.
[0464] Protective film C: triacetyl cellulose (TAC) film (thickness 20 μm) with a rigidity of 98960 N / m.
[0465] ·Releasable film D: triacetyl cellulose (TAC) film. (Thickness 80 μm)
[0466] · Substrate film E: triacetyl cellulose (TAC) film (thickness 80 μm) with a rigidity of 395840 N / m.
[0467] Protective film F: Polyethylene terephthalate (PET) film (thickness 38 μm) with a rigidity of 193420 N / m.
[0468] (Production of Polarizing Laminated Body (Linear Polarizing Plate) 1)
[0469] A protective film A was laminated to one side of the prepared polarizer 1 with a water-based adhesive, and a releasable film D was laminated to the side opposite to the protective film A with pure water using a roll laminator, and then dried at 80° C. for 3 minutes. Then, a protective film F was laminated to the protective film A with an adhesive layer, and the releasable film D was peeled off from the polarizer to obtain a polarizing laminate 1 having a protective film laminated only on one side of the polarizer. The polarizing laminate 1 is laminated with a linear polarizer, an adhesive layer, a protective film A, an adhesive layer, and a protective film F in this order.
[0470] (Production of Polarizing Laminated Body (Linear Polarizing Plate) 2)
[0471] A protective film B was laminated to one side of the prepared polarizer 1 by means of a water-based adhesive, and a protective film C was laminated to the side opposite to the protective film B by means of a water-based adhesive using a roll laminating machine, and then a drying treatment was performed at 80° C. for 3 minutes. Then, a protective film F was laminated to the protective film B by means of an adhesive layer, and a polarizing laminate 2 having protective films laminated on both sides of the polarizer was obtained. The polarizing laminate 2 is laminated with the protective film F, the adhesive layer, the protective film B, the adhesive layer, the polarizer, the adhesive layer, and the protective film C in this order.
[0472] (Manufacture of Laminated Film 1 Including First Liquid Crystal Retardation Layer (1 / 2 Wavelength Retardation Layer))
[0473] (Preparation of the first liquid crystal retardation layer forming composition)
[0474] A polymerizable liquid crystal compound (A1) and a polymerizable liquid crystal compound (A2) having the structures shown below were prepared respectively. The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) were prepared according to the method described in Japanese Patent Application Laid-Open No. 2010-244038.
[0475] Polymerizable liquid crystal compound (A1):
[0476] [Chemical formula 9]
[0477]
[0478] Polymerizable liquid crystal compound (A2):
[0479] [Chemical formula 10]
[0480]
[0481] The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) were mixed in a mass ratio of 80:20 to obtain a mixture. 0.1 parts of a leveling agent "MEGAFACE F-556" (manufactured by DIC) and 2.5 parts of "Omnirad907" (manufactured by IGM Resin BV) as a photopolymerization initiator were added to 100 parts of the obtained mixture, and 0.1 parts of the ionic compound (B) shown below were added. In addition, 650 parts of cyclopentanone were added to 100 parts of the mixture, and stirred at a temperature of 80°C for 1 hour to prepare a first liquid crystal phase difference layer forming composition.
[0482] Ionic compounds (B)
[0483] [Chemical formula 11]
[0484]
[0485] (Preparation of Laminated Film 1 of Substrate / Alignment Layer / First Liquid Crystal Retardation Layer)
[0486] After corona treatment was performed on the TAC film (substrate film E) using a corona treatment device (AGF-B 1 0; manufactured by Kasuga Electric Co., Ltd.), an oriented polymer composition (A) was applied, and after heating and drying, an oriented polymer oriented layer (A) with a thickness of 100 nm was formed. The surface of the oriented layer (A) was subjected to a rubbing treatment at an angle of 75° to the longitudinal direction of the substrate film E, and the first liquid crystal phase difference layer forming composition was applied thereon by a bar coater, and dried at 120°C for 2 minutes to obtain a dry film. Using a high-pressure mercury lamp ("Unicure VB-15201BY-A" manufactured by USHIO Electric Co., Ltd.), the dry film was irradiated with ultraviolet light with an exposure amount of 1000mJ / cm2 (based on 365nm) at a temperature of 80°C under a nitrogen atmosphere, thereby forming a first liquid crystal phase difference layer cured in a state where the optical axis of the polymerizable liquid crystal compound is oriented in a horizontal direction relative to the surface of the substrate film E, and a laminated film 1 as an optical film was obtained. The laminated film 1 has a layer structure of base film E / alignment layer (A) / first liquid crystal retardation layer.
[0487] The thickness of the obtained first liquid crystal phase difference layer was measured with a laser microscope, and the result was 1.8 μm. The in-plane phase difference value of the laminated film 1 was measured using KOBRA-WR manufactured by Prince Instruments Co., Ltd. As a result, the in-plane phase difference value at a wavelength of 550 nm was Re(550)=270 nm. It should be noted that the phase difference value of the TAC film as the substrate film E at a wavelength of 550 nm is approximately 0, so it has no effect on the optical properties of the laminated film 1. The orientation angle relative to the length direction of the substrate film E is 75°.
[0488] (Preparation of Laminated Film 2 Including Second Liquid Crystal Retardation Layer (1 / 4 Wavelength Retardation Layer))
[0489] (Preparation of Oriented Polymer Composition (A) (Oriented Layer Forming Composition (A)))
[0490] Water was added to commercially available polyvinyl alcohol (polyvinyl alcohol 1000 completely saponified type, manufactured by Wako Pure Chemical Industries, Ltd.), and the mixture was heated at 100° C. for 1 hour to obtain an oriented polymer composition (A).
[0491] (Preparation of Second Liquid Crystal Retardation Layer-Forming Composition)
[0492] To 100 parts of the polymerizable liquid crystal compound Paliocolor LC242 (manufactured by BASF Japan) shown below, 0.1 parts of a leveling agent "BYK-361N" (manufactured by BYK-Chemie) and 2.5 parts of "Omnirad907" (manufactured by IGM Resin BV) as a photopolymerization initiator were added. In addition, to 100 parts of the above-mentioned polymerizable liquid crystal compound, 400 parts of propylene glycol 1-monomethyl ether 2-acetate (PGME) were added, and the mixture was stirred at a temperature of 80°C for 1 hour to prepare a composition for forming a second liquid crystal phase difference layer.
[0493] (Preparation of Laminated Film 2 of Substrate / Alignment Layer / Second Liquid Crystal Retardation Layer)
[0494] An oriented polymer composition (A) is applied to a triacetylcellulose film (substrate film E) cut into a rectangular shape, and heated and dried to form an oriented layer (A) with a thickness of 100 nm. A friction treatment is applied to the surface of the oriented layer (A) at an angle of 15° to the length direction of the above-mentioned substrate film E film, and a composition for forming a second liquid crystal phase difference layer is applied thereon using a rod coater. The obtained coating layer is dried at 100°C for 1 minute and then cooled to room temperature to obtain a dried film. Next, a high-pressure mercury lamp ("Unicure VB-15201BY-A" manufactured by USHIO Electric Co., Ltd.) is used to irradiate the dried film with 1000mJ / cm2 (based on 365nm) of ultraviolet rays in a nitrogen atmosphere, thereby forming a second liquid crystal phase difference layer (horizontally oriented liquid crystal phase difference film) solidified in a state where the polymerizable liquid crystal compound is oriented in a horizontal direction in the plane of the substrate film E, and a laminated film 2 having a structure of substrate film E / oriented layer / second liquid crystal phase difference layer is obtained.
[0495] The thickness of the obtained second liquid crystal phase difference layer was measured with a laser microscope, and the result was 1.0 μm. The in-plane phase difference value of the laminated film 2 was measured using KOBRA-WR manufactured by Prince Instruments Co., Ltd. As a result, the in-plane phase difference value at a wavelength of 550 nm was Re(550)=140 nm. It should be noted that the phase difference value of the TAC film as the substrate layer at a wavelength of 550 nm is approximately 0, so it has no effect on the optical properties. The orientation angle is 15° relative to the length direction of the substrate layer. The second liquid crystal phase difference layer has positive wavelength dispersion.
[0496] (Preparation of Active Energy Ray-Curing Adhesive A)
[0497] The following components were blended and mixed, and then degassed to prepare an active energy ray-curable adhesive A.
[0498] [Cationically polymerizable compound]
[0499] Neopentyl glycol diglycidyl ether (trade name: EX-211L, manufactured by Nagase ChemteX Co., Ltd.): 30 parts by mass
[0500] · 3-Ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane (trade name: OXT-221, manufactured by Toagosei Co., Ltd.): 13 parts by mass
[0501] Bisphenol A type epoxy resin (trade name: EP-4100E, ADEKA Corporation, viscosity 13 Pa·s (temperature 25° C.)): 45 parts by mass
[0502] Aromatic oxetane compound (trade name: TCM-104, manufactured by TRONLY): 12 parts by mass
[0503] [Photocationic polymerization initiator]
[0504] CPI-100P, manufactured by San-Apro Co., Ltd., 50% propylene carbonate solution: 2.25 parts by mass (solid content)
[0505] [Photosensitizing agent]
[0506] 1,4-diethoxynaphthalene: 1 part by mass
[0507] (Preparation of Active Energy Ray-Curing Adhesive B)
[0508] The components shown below were mixed to prepare an active energy ray-curable adhesive B.
[0509] 3',4'-Epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (trade name: CEL2021P, manufactured by Daicel Corporation): 70 parts by mass
[0510] Neopentyl glycol diglycidyl ether (trade name: EX-211, manufactured by Nagase ChemteX Corporation): 20 parts by mass
[0511] 2-Ethylhexyl glycidyl ether (trade name: EX-121, manufactured by Nagase ChemteX Corporation): 10 parts by mass
[0512] Cationic polymerization initiator (trade name: CPI-100, 50% solution, manufactured by San-Apro Co., Ltd.): 4.5 parts by mass (substantial solid content: 2.25 parts by mass)
[0513] 1,4-diethoxynaphthalene: 2.0 parts by mass
[0514] (Fabrication of Laminated Film Z Including Phase Element)
[0515] The surface of the first liquid crystal phase difference layer (1 / 2 wavelength phase difference layer) of the laminated film 1 and the surface of the second liquid crystal phase difference layer (1 / 4 wavelength phase difference layer) of the laminated film 2 are respectively subjected to corona treatment. The corona-treated surface of the laminated film 1 and the corona-treated surface of the laminated film 2 are bonded together using the active energy ray-curable adhesive A prepared above so that the angle formed by the slow axes of the two liquid crystal phase difference layers is 60°. Then, from the side of the 1 / 4 wavelength phase difference layer as the second liquid crystal phase difference layer, an ultraviolet irradiation device [manufactured by Fusion UV Systems Co., Ltd.] is used to irradiate with ultraviolet light at a cumulative light amount of 400mJ / cm2 (UV-B) to cure the active energy ray-curable adhesive A to form a phase element. The bonding is performed using a laminator, and the active energy ray-curable adhesive A is applied in such a way that the thickness of the cured adhesive layer becomes 3μm. Thus, a laminated film Z of a phase element was obtained, which was sequentially laminated with substrate film E / orientation layer / first liquid crystal phase difference layer (1 / 2 wavelength phase difference layer) / layer of a cured product of active energy ray-curable adhesive A / second liquid crystal phase difference layer (1 / 4 wavelength phase difference layer) / orientation layer / substrate film E. The total thickness of the first liquid crystal phase difference layer (1 / 2 wavelength phase difference layer), the phase element adhesive layer and the second liquid crystal phase difference layer (1 / 4 wavelength phase difference layer) was 6 μm.
[0516] <Production of a circular polarizing plate raw material roll>
[0517] [Example 1]
[0518] The substrate film E and the orientation layer on the side of the first liquid crystal phase difference layer (1 / 2 wavelength phase difference layer) of the above-made stacked film Z containing the phase element are peeled off, and an active energy ray-curable adhesive A is applied on the exposed first liquid crystal phase difference layer (1 / 2 wavelength phase difference layer) using a rod coater, and then bonded to the polarizer surface of the above-made polarization stack 1 to obtain an optical stack.
[0519] The obtained optical laminate is composed of a polarizing laminate 1 (protective film F, adhesive layer, protective film A, polarizer adhesive layer, polarizer), uncured active energy ray-curable adhesive A, and a phase element (a first liquid crystal phase difference layer (1 / 2 wavelength phase difference layer), a layer of a cured product of the active energy ray-curable adhesive A, a second liquid crystal phase difference layer (1 / 4 wavelength phase difference layer), an orientation layer), and a substrate film E.
[0520] Then, ultraviolet rays (under nitrogen atmosphere, wavelength: 365 nm, cumulative light intensity at wavelength 365 nm: 1000 mJ / cm) were irradiated from the phase element side using a high pressure mercury lamp (Unicure VB-15201BY-A, manufactured by USHIO Electric Co., Ltd.). 2 ),along Figure 5 The circular polarizing plate (1) is transported and wound along a transport path to obtain a raw material roll. The 1 / 2 wavelength phase difference layer and the polarizing laminate are bonded in such a way that the angle between the slow axis of the 1 / 2 wavelength phase difference layer and the transmission axis of the polarizing plate is 15°. Each bonding surface is subjected to a corona treatment. Figure 5 The wrap angle of the conveying roller R2 in contact with the polarizing laminate in the conveying path is 28°. The total rigidity (Young's modulus × thickness) of the protective film F and the protective film A is 223,190 N / m, and the rigidity of the base film E is 395,840 N / m. The shear stress α of the cured layer of the active energy ray-curable adhesive A is 10 Pa.
[0521] The raw material roll of the circular polarizing plate (1) was visually inspected by the above-mentioned defect inspection method, and the results showed that there were no periodic concave defects with a maximum depth exceeding 500 nm on the surface of the polarization stack 30 side in the layer 40 of active energy ray-curable adhesive and on the surface of the phase element 50 side in the layer 40 of active energy ray-curable adhesive.
[0522] [Example 2]
[0523] exist Figure 5 In the conveying path, the wrap angle of the conveying roller R2 was set to 74°, and the same operation as in Example 1 was performed to obtain a raw material roll of a circular polarizing plate (2). The total rigidity of the protective film F and the protective film A was 223,190 N / m, and the rigidity of the base film E was 395,840 N / m. The shear stress α of the cured layer of the active energy ray-curable adhesive A was 10 Pa.
[0524] The raw material roll of the circular polarizing plate (2) was visually inspected by the above-mentioned defect inspection method, and the results showed that there were no periodic concave defects with a maximum depth exceeding 500 nm on the surface of the polarization stack 30 side in the layer 40 of active energy ray-curable adhesive and the surface of the phase element 50 side in the layer 40 of active energy ray-curable adhesive.
[0525] [Example 3]
[0526] exist Figure 5 In the conveying path, the wrap angle of the conveying roller R2 was set to 114°, and the same operation as in Example 1 was performed to obtain a raw material roll of a circular polarizing plate (3). The total rigidity of the protective film F and the protective film A was 223,190 N / m, and the rigidity of the base film E was 395,840 N / m. The shear stress of the cured layer of the active energy ray-curable adhesive A was 10 Pa.
[0527] The raw material roll of the circular polarizing plate (3) was visually inspected by the above-mentioned defect inspection method, and the results showed that there were no periodic concave defects with a maximum depth exceeding 500 nm on the surface of the polarization stack 30 side in the layer 40 of active energy ray-curable adhesive and the surface of the phase element 50 side in the layer 40 of active energy ray-curable adhesive.
[0528] [Comparative Example 1]
[0529] A raw material roll of a circular polarizing plate (C1) was obtained in the same manner as in Example 1 except that the wrap angle of the conveying roller R2 was set to 164°. The total rigidity of the pellicle F and the protective film A was 223,190 N / m, and the rigidity of the base film E was 395,840 N / m. The shear stress of the cured layer of the active energy ray-curable adhesive A was 10 Pa.
[0530] The original roll of the circular polarizing plate (C1) was visually inspected by the above-mentioned defect inspection method. As a result, the number of visually observable periodic concave defects was 7.7 pieces / m. 2 The depths of all the concave defects were measured. As a result, the concave defects were present on the surface of the active energy ray-curable adhesive layer 40 on the polarizing laminate 30 side, and the maximum depths of all the concave defects exceeded 500 nm.
[0531] 〔Reference Example 1〕
[0532] A polarizing laminate 2 is used instead of the polarizing laminate 1, and the first liquid crystal phase difference layer (1 / 2 wavelength phase difference layer) exposed in the phase element is bonded to the protective film C surface of the polarizing laminate 2. Except for this, the same operation as in Comparative Example 1 is performed to obtain a raw material roll of a circular polarizing plate (R1). The optical laminate obtained before irradiation with active energy rays is composed of a polarizing laminate 2 (protective film F, adhesive layer, protective film B, adhesive layer, polarizer, adhesive layer, protective film C), uncured active energy ray-curing adhesive A, and a phase element (first liquid crystal cured material layer (1 / 2 wavelength phase difference layer, layer of cured material of layer A of active energy ray-curing adhesive, second liquid crystal cured material layer (1 / 4 wavelength phase difference layer), orientation layer), and substrate film E.
[0533] The total rigidity of the pellicle F, the protective films B, and the protective films C in the linear polarizing plate 1 was 351,920 N / m, and the rigidity of the base film was 395,840 N / m. The shear stress of the cured layer of the active energy ray-curable adhesive A was 10 Pa.
[0534] The raw material roll of the circular polarizing plate (R1) was visually inspected using the above-mentioned defect inspection method, and the results showed that there were no periodic concave defects with a maximum depth exceeding 500 nm on the surface of the polarization stack 30 side of the layer 40 of the active energy ray-curable adhesive and on the surface of the phase element 50 side of the layer 40 of the active energy ray-curable adhesive.
[0535] 〔Reference Example 2〕
[0536] A circular polarizing plate (R2) was obtained in the same manner as in Comparative Example 1 except that the active energy ray-curable adhesive layer B was used instead of the active energy ray-curable adhesive layer A when the linear polarizing plate 1 and the retardation layer structure A with a substrate layer were bonded together.
[0537] The optical laminate obtained before irradiation with active energy rays is composed of a linear polarizing plate 1 (protective film F, adhesive layer, protective film B, adhesive layer, polarizer, adhesive layer, protective film C), uncured active energy ray-curable adhesive B, and a phase element (a first liquid crystal cured material layer (a 1 / 2 wavelength phase difference layer, a layer of a cured material of layer A of the active energy ray-curable adhesive, a second liquid crystal cured material layer (a 1 / 4 wavelength phase difference layer), an orientation layer), and a substrate film E.
[0538] The total rigidity of the pellicle F and the protective film A was 223,190 N / m, and the rigidity of the base film E was 395,840 N / m. The shear stress of the cured layer of the active energy ray-curable adhesive B was 13405 Pa.
[0539] The raw material roll of the circular polarizing plate (R2) was visually inspected using the above-mentioned defect inspection method, and the results showed that there were no periodic concave defects with a maximum depth exceeding 500 nm on the surface of the polarization stack 30 side of the layer 40 of the active energy ray-curable adhesive and on the surface of the phase element 50 side of the layer 40 of the active energy ray-curable adhesive.
[0540] The results are summarized in Table 1.
[0541] [Table 1]
[0542]
[0543] Description of Reference Numerals
[0544] 30...Polarizing laminate (linear polarizing plate), 32...Linear polarizing plate, 34...First polarizing plate protective film (protective film), 36...Second polarizing plate protective film (protective film), 37...Protective film (protective film), 40...Active energy ray-curable adhesive layer, 50...Phase element, 40',...Active energy ray-curable adhesive cured layer, 52...First liquid crystal phase difference layer, 58...Second liquid crystal phase difference layer, 54...Orientation layer, 56...Phase element adhesive layer, 80...Substrate layer, 100...Optical laminate, 100'...Circular polarizing plate, θ, α...Wrap angles, R1~R2...Conveying rollers.
Claims
1. A method for manufacturing a raw material roll of a circular polarizing plate, comprising: A step of preparing an optical laminate, the optical laminate comprising, in order, a polarizing laminate, a layer of an active energy ray-curable adhesive, a phase element comprising one or more liquid crystal phase difference layers, and a substrate layer, the polarizing laminate comprising a linear polarizer and one or more protective films; a step of irradiating the optical layered body with active energy rays to cure the layer of the active energy ray-curable adhesive; as well as a step of conveying the optical layered body while bringing it into contact with the surface of at least one conveying roller after the irradiation, The cured product of the active energy ray-curable adhesive has a shear stress α of 100 Pa or less at 25° C., The shear stress α refers to the maximum stress when a cured product of the active energy ray-curable adhesive in the shape of a disk having a diameter of 8 mm and a thickness of 5 μm is clamped between a pair of parallel plates and vibrated about the central axis of the disk at a rotation angle of 1 mrad and a frequency of 1 Hz to impart a torsional moment. The total rigidity value of each of the protective films in the polarizing laminate is 250000 N / m or less, In the conveying step, at least one conveying roller is in contact with the polarizing laminate of the optical laminate, and a wrap angle of the conveying roller in contact with the polarizing laminate of the optical laminate is 150° or less. In the conveying process, when at least one conveying roller is in contact with the substrate layer of the optical stack and the rigidity value of the substrate layer is less than 250,000 N / m, further in the conveying process, the wrap angle of the conveying roller in contact with the substrate layer of the optical stack is less than 150°.
2. The method according to claim 1, wherein: In the irradiation step, the optical layered body is irradiated with the active energy ray from the substrate layer side.
3. A raw material roll of a circular polarizing plate, which comprises, in order, a polarizing laminate, a layer of a cured product of an active energy ray-curable adhesive, and a phase element comprising one or more liquid crystal phase difference layers, wherein the polarizing laminate has a linear polarizer and one or more protective films, The total rigidity value of each of the protective films in the polarizing laminate is 250000 N / m or less, The cured product of the active energy ray-curable adhesive has a shear stress α of 100 Pa or less at 25° C., The shear stress α refers to the maximum stress when a cured product of the active energy ray-curable adhesive in the shape of a disk having a diameter of 8 mm and a thickness of 5 μm is clamped between a pair of parallel plates and vibrated about the central axis of the disk at a rotation angle of 1 mrad and a frequency of 1 Hz to impart a torsional moment. The surface of the layer of the cured product of the active energy ray-curable adhesive on the side facing the polarizing laminate does not have recessed portions having a maximum depth exceeding 500 nm that are periodically formed along the longitudinal direction of the circularly polarizing plate.
4. The circular polarizing plate raw material roll according to claim 3, wherein: The surface of the layer of the cured product of the active energy ray-curable adhesive on the side opposite to the phase element does not have recessed portions having a maximum depth exceeding 500 nm that are periodically formed along the longitudinal direction of the circularly polarizing plate.
Citation Information
Patent Citations
Production of polymer and precursor thereof
JP1989240517A
Plating composition and plated object
JP1991014882A
Thermoplastic resin molded article
JP1991122137A
Polarizing plate and its manufacturing method
JP2005208456A
Polarizer plate and method for manufacturing the same
JP2010191389A